Guide to Archival Ressources at McGill University / Guide des sources d'archives à l'Université McGill - Caya, Marcel (Archives de l'Université McGill, 1985)
Keywords: Université McGill

Le département de langue et littérature françaises de l'Université McGill de 1853 à nos jours - Lamonde, Yvan (Université McGill - Département de langue et littérature françaises, 2013)
Keywords: Langue; Université McGill

L'université McGill a 150 ans - Gourdeau-Coté, Suzanne; Smith, André (Forces, 1971)
Keywords: Université McGill

L'Université McGill et la société québécoise francophone, 1951-1969 - Leduc, Bernard (Université de Montréal, 1999)
Keywords: Université McGill

Esprit universitaire ou esprit étudiant. La recherche d'identité des étudiants de l'Université McGill et de l'Université de Montréal (1900-1960) - Hébert, Karine (Les transformations des universités du XIIIe au XXIe siècle, 2006)
Keywords: Université McGill; Université de Montréal; Étudiants

Montréal, l'Université McGill et F. A. Trottier des Rivières - Audet, Francis-J. (Missisquoi - A Store of Memories - Missisquoi County Historical Society, 1972)
Keywords: Trottier des Rivières, F. A.; Université McGill

Histoire comparée de la Faculté de génie de l'Université McGill et de l'École Polytechnique - Tourigny, Paul (Université de Montréal, 1980)
Keywords: Ingénieurs; Université McGill; École polytechnique

Carabines, poutchinettes co-eds ou freschettes sont-elles des étudiantes? Les filles à l’Université McGill et à l’Université de Montréal (1900-1960) - Hébert, Karine (Revue d'histoire de l'Amérique française, 2004)
Keywords: Femmes; Université McGill; Université de Montréal; Étudiants

Savoir et pouvoir dans l'univers des disciplines paramédicales: la formation en physiothérapie et en diététique à l'Université McGill, 1940-1970 - Fahmy-Eid, Nadia; Collin, Johanne (Histoire sociale / Social History, 1989)
Keywords: Diététique; Femmes; Physiothérapie; Université McGill

The History of the Alumnae Society of McGill University, 1889-1959 (Université McGill, 1959)
Keywords: Université McGill

McGill University at War, 1914-1918, 1939-1945 - Fetherstonhaugh, R. C. (Université McGill, 1947)
Keywords: Guerre; Mortalité; Université McGill

The Osler Library (Université McGill, 1979)
Keywords: Bibliothèque Osler; Médecine; Université McGill

A Guide to McGill University Calendars for the Academic Years 1853-54 to 1975-76 - Wray, Arpi (Archives de l'Université McGill, 1977)
Keywords: Université McGill

Scrapbooks in the McGill University Archives, 1843-1969 - Sparks, Ann (Archives de l'Université McGill, 1971)
Keywords: Université McGill

A Preliminary List of Papers Transferred to the McGill University Archives by the Secretary-General, Accession No. 1766 - Kense, Françoise; Kuplowsky, Walter (Archives de l'Université McGill, 1974)
Keywords: Université McGill

A Preliminary Guide to the Records of McGill Libraries, Record Group 40 - Alain, Robert (Archives de l'Université McGill, 1973)
Keywords: Université McGill

A Preliminary Description of McGill Teacher Training Records 1888-1938 - Davis, Davena (Archives de l'Université McGill, 1970)
Keywords: Enseignants; Université McGill

Sources in the Law Library of McGill University for a Reconstruction of the Legal Culture of Quebec, 1760-1890 - Baker, Blaine; Masciotra, Vince; Young, Brian (Éditions du MBHP, Université McGill, 1987)
Keywords: Droit; Université McGill

McGill Campus. Historical Development - Weiner, Michaela (Université McGill, 1979)
Keywords: Université McGill

McGill since 1920 - Yulen, Audrey (Université McGill, 1958)
Keywords: Université McGill

List of Incoming Correspondence of McGill Principal Sir William Peterson, Record Group 2P, Accession 641, Bundles 15-17 - Rubinstein, Renée (Archives de l'Université McGill, 1977)
Keywords: Peterson, William; Université McGill

Incoming Correspondence of Sir William Peterson, C.B., Record Group 2P, Accession No. 641, Bundles 3, 4 and 5 - Martyn, Olive M. (Archives de l'Université McGill, 1977)
Keywords: Peterson, William; Université McGill

A Preliminary List of the Incoming Correspondence of Sir William Peterson, C.B., Record Group 2 p, Accession 641, Bundles 6A, 7, 8 - Douglas, Lawrence Taylor (Archives de l'Université McGill, 1977)
Keywords: Peterson, William; Université McGill

The Faculty of Religious Studies, McGill University, 1948-1978 - Markell, H. Keith (Université McGill, Faculty of Religious Studies, 1979)
Keywords: Théologie; Université McGill

James McGill: A Critical Biographical Study - Macsporran, Maysie Steel (Université McGill, 1930)
Keywords: McGill, James; Université McGill

A Preliminary List of the Official Papers of Charles Henry Gould, Record Group 40, Accession 654, Items 1-46, 1895 - Tallman, Julie (Archives de l'Université McGill, 1973)
Keywords: Gould, Charles Henry; Université McGill

Preliminary List of Incoming Letters of McGill Librarian C. H. Gould. Record Group 40, Accession 654, 1901, M-S, Items 1-153 - Stern, Claire (Archives de l'Université McGill, 1977)
Keywords: Gould, Charles Henry; Université McGill

A Preliminary List of the Incoming Letters of the McGill Librarian Charles H. Gould, Record Group 40, Accession 654/1898, A-C, Items 1-162 - Rooney, Thomas (Archives de l'Université McGill, 1974)
Keywords: Gould, Charles Henry; Université McGill

A Preliminary List of the Incoming Letters of McGill Librarian Charles Henry Gould, 1896, Record Group 40, Accession 654 - Mcleod, Norman (Archives de l'Université McGill, 1974)
Keywords: Gould, Charles Henry; Université McGill

Preliminary List of Incoming Letters of McGill Librarian C. H. Gould, 1899, record group 40, Accession 654 - Dyck, Jacqueline (Archives de l'Université McGill, 1974)
Keywords: Gould, Charles Henry; Université McGill

Preliminary List of Incoming Letters of McGill Librarian C. H. Gould, 1906, O-Z, Record Group 40, Accession 654 - Forget, Gérald (Archives de l'Université McGill, 1977)
Keywords: Gould, Charles Henry; Université McGill

Separate or Mixed: The Debate over Co-Education at McGill University - Lapierre, Paula J. S. (Université McGill, 1983)
Keywords: Femmes; Université McGill

Interkulturelle Landeskunde im Bereich des Deutschen als Fremdsprache an kanadischen Hochschulen: Dokumentation einer Fallstudie am Department of German Studies der McGill University, Montreal, Quebec, Kanada - Mollinger, Karin (Université McGill, 1996)
Keywords: Allemands; Université McGill

The Educational Function of Museums in the Vicinity of Montreal: With Special Reference to Historical Museums and Sites - Ferrabee, Henry Gilbert (Université McGill, 1953)
Keywords: Musées; Université McGill

McGill University’s racial exclusion of Japanese Canadians, 1943-1945 - Elsworthy, Tess (Université McGill, 2020)
Keywords: Japonais; Université McGill

The Story of Old McGill and Its Origin - Altman, Sarina (Université McGill, 1960)
Keywords: Université McGill; Étudiants

A Preliminary Description of Papers Relating to Redpath Museum, Accession 1476 - 1880-1966 - Morgan, Patricia Ann (Archives de l'Université McGill, 1973)
Keywords: Musées; Redpath (musée); Université McGill

Racialized social relations in higher education: Black student and faculty experiences of a Canadian university - Hampton, Rosalind (Université McGill, 2017)
Keywords: McGill Daily; McGill, James; Noirs; Université McGill

Sir William C. Macdonald; Benefactor to Education - Epstein, Murray Hart (Université McGill, 1969)
Keywords: Macdonald, William C.; Université McGill

Ancient Greek Gold and Silver Coins in the McGill University Collection - Shlosser, Franziska E. (Université McGill, 1971)
Keywords: Grecs; Numismatie; Université McGill

Sir William Osler's Contribution to Medical Education with Special Emphasis on Clinical Training and the Dilemna of Whole-Time Professorship - Wise, Audrey Maureen (Université McGill, 1978)
Keywords: Médecine; Osler, William; Université McGill

The McGill Normal School: A Brief History 1857-1907 - Paradissis, Elia Alexandra (Université McGill, 1982)
Keywords: Enseignants; Université McGill; Écoles normales

The Development of Higher Education for Women at McGill University from 1857 to 1899 with Special Reference to the Role of Sir John William Dawson - Ronish, Donna Ann (Université McGill, 1972)
Keywords: Dawson, William; Femmes; Université McGill

The Relationship between Student Activism and Change in the University: With Particular Reference to McGill University in the 1960s - Sheppard, Peggy (Université McGill, 1989)
Keywords: Associations étudiantes; Université McGill; Étudiants

A Guide to Transcripts of Documents Concerning McGill College and the Royal Institute for the Advancement of Learning, 1842-1849 - King, John (Archives de l'Université McGill, 1977)
Keywords: Royal Institution for the Advancement of Learning; Université McGill

"The Big Ladies' Hotel": Gender, Residence, and Middle-Class Montreal: A Contextual Analysis of the Royal Victoria College, 1899-1931 - Miller, Deborah L. (Université McGill, 1998)
Keywords: Femmes; Royal Victoria College; Université McGill

The Women's College with Special Reference to Royal Victoria College, McGill University - Dubkiewicz, Zina (Université McGill, 1982)
Keywords: Femmes; Royal Victoria College; Université McGill

The Women's College, with Special Reference to Royal Victoria College, McGill University - Dudkiewicz, Zina (Université McGill, 1982)
Keywords: Femmes; Royal Victoria College; Université McGill

A Preliminary Guide to the Files of Principals Sir Arthur Currie 1920-33, A. E. Morgan 1935-37, Lewis William Douglas 1937-39, Record groups 2C, 2N, and 2D, Accession 641 - Alain, Robert (Archives de l'Université McGill, 1974)
Keywords: Currie, Arthur; Douglas, Lewis William; Morgan, A. E.; Université McGill

Étude patrimoniale des sites et des bâtiments hospitaliers reliés à l'Université McGill - Lachapelle, Jacques; Bisson, Pierre-Richard (1997)
Keywords: Hôpital Général; Hôpitaux; Royal Victoria Hospital

Financial Support for Post-Graduate Students and the Development of Scientific Research in Canada - Gingras, Yves (Youth, University and Canadian Society: Essays in the Social History of Higher Education, 1989)
Keywords: Université McGill

McGill Between the Wars - Thompson, David (McGill: The Story of a University, 1960)
Keywords: Université McGill

Four Principals of McGill : a Memoir, 1929-1963 - Mcmurray, Dorothy (Graduates' Society of McGill University, 1974)
Keywords: Université McGill

The Building of McGill University - Traquair, Ramsay (Journal, Royal Architectural Institute of Canada, 1925)
Keywords: Université McGill

The Link with the Future, 1945-1959 - James, F. Cyril (McGill: The Story of a University, 1960)
Keywords: Université McGill

The History of McGill in Relation to the Social, Economic and Cultural Aspects of Montreal and Quebec - Frost, Stanley Brice (Commission d'étude sur les universités, 1979)
Keywords: Université McGill

McGill University: For the Advancement of Learning. Vol. 2: 1895-1971 - Frost, Stanley Brice (McGill-Queen's University Press, 1984)
Keywords: Université McGill

The McGill You Knew: An Anthology of Memories, 1920-1960 - Collard, Edgar Andrew (Longman Canada, 1975)
Keywords: Université McGill

McGill and Its Story, 1821-1921 - Macmillan, Cyrus (Oxford University Press, 1921)
Keywords: Université McGill

The Origins of McGill - Maclennan, Hugh (McGill: The Story of a University, 1960)
Keywords: Université McGill

McGill: The Story of a University - Maclennan, Hugh (G. Allen and Unwin, 1960)
Keywords: Université McGill

McGill University: For the Advancement of Learning. 1801-1895 - Frost, Stanley Brice (McGill-Queen's University Press, 1980)
Keywords: Université McGill

Oldest McGill - Collard, Edgar Andrew (MacMillan of Canada, 1946)
Keywords: Université McGill

Bibliography of McGill Northern Research: 1887-1975 (The Centre, 1976)
Keywords: Université McGill

George Heath MacDonald (Class of 1911): The Story of One Graduate from McGill University's School of Architecture - Johnson, Percy (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Université McGill

Teaching the History of Architecture at McGill, 1896-1903 - Schoenauer, Norbert (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Université McGill

The First Leaders of McGill's School of Architecture: Stewart Henbest Capper, Percy Nobbs, and Ramsay Traquair - Gournay, Isabelle (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Université McGill

James McGill of Montreal - Frost, Stanley Brice (McGill-Queen's University Press, 1995)
Keywords: McGill, James; Université McGill

James McGill and the University of McGill College - Dawson, John William (Barnard's American Journal of Education, 1863)
Keywords: McGill, James; Université McGill

James McGill and the Origin of his University - Dawson, J. W. (s.é., 1870)
Keywords: McGill, James; Université McGill

James McGill and the Origin of his University - Dawson, John William (New Dominion Monthly, 1870)
Keywords: McGill, James; Université McGill

Attention continue - Diodati, Giovanni (Continuité, 2016)
Keywords: Conservation; Université McGill

Parts in Play: The Rosalynde Osborne Stearn Collection at McGill University - Flegel, Loretta (Université Concordia, 2003)
Keywords: Théâtre; Université McGill

La physique à McGill entre 1920 et 1940: la réception de la mécanique quantique par une communauté scientifique périphérique - Gingras, Yves (HSTC Bulletin, 1981)
Keywords: Physique; Université McGill

A Scout of the Past: Ramsay Traquair and the Legacy of the National Art Survey of Scotland in Quebec - Murray, Irena (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Université McGill; Écossais

McGill Medicine. Vol. 2 - 1885-1936 - Hanaway, Joseph; Cruess, Richard L.; Darragh, James (McGill-Queen's University Press, 2006)
Keywords: Médecine; Université McGill

McGill Medicine. Vol. 1 - The First Half Century, 1829-1885 - Hanaway, Joseph; Cruess, Richard L. (McGill-Queen's University Press, 1996)
Keywords: Médecine; Université McGill

Science and Engineering at McGill and Queen's Universities and the University of Toronto, 1880s to 1920s - Creet, Mario (Université Queen's, 1993)
Keywords: Ingénieurs; Université McGill

In Caps and Gowns: The Story of the School for Graduate Nurses. McGill University 1920-1964 - Tunis, B. L. (McGill University Press, 1966)
Keywords: Infirmières; Université McGill

The Story of Women Associates of McGill - Maas, C. E. (L'Association, 1968)
Keywords: Femmes; Université McGill

Teacher Education at McGill - Munroe, D. (McGill Journal of Education, 1971)
Keywords: Enseignants; Université McGill

We Walked Very Warily: A History of Women at McGill - Gillett, Margaret (Eden Press Women's Publications, 1981)
Keywords: Femmes; Université McGill

A Fair Shake: Autobiographical Essays by McGill Women - Gillett, Margaret; Sibbald, Kay (Eden Press, 1984)
Keywords: Femmes; Université McGill

Law at McGill: Past, Present and Future - Frost, Stanley Brice; Johnston, David L. T. (Revue de droit de McGill / McGill Law Journal, 1981)
Keywords: Droit; Université McGill

Psychology at McGill - Ferguson, George A. (History of Academic Psychology in Canada, 1981)
Keywords: Psychologie; Université McGill

The McGill Student Body: Past and Future Enrolment - Frost, Stanley Brice; Rosenberg, Sheila (McGill Journal of Education, 1980)
Keywords: Université McGill; Étudiants

One Hundred Years of Engineering at McGill - Collins, Peter (Engineering Journal, 1972)
Keywords: Ingénieurs; Université McGill

Reminiscences of the Medical School of McGill University - Maccallum, D. C. (McGill University Magazine, 1903)
Keywords: Médecine; Université McGill

On the Past, Present, and Future of the Faculty of Medecine of McGill University; an Introductory Lecture Delivered at the Opening of the Session 1866-67 - Hall, Archibald (Canada Medical Journal and Monthly Record of Medical and Surgical Science, 1866)
Keywords: Médecine; Université McGill

The Early Days of Law Teaching at McGill - Frost, Stanley Brice (Dalhousie Law Journal, 1984)
Keywords: Droit; Université McGill

An Historical Sketch of the Medical Faculty of McGill University - Abbott, M. E. (Montreal Medical Journal, 1902)
Keywords: Médecine; Université McGill

Early American Medical Schools: the Faculty of Medicine of McGill University - Abbott, M. E. (Surgery, Gynecology and Obstetrics, 1935)
Keywords: Médecine; Université McGill

The Four Founders - Quinn, R. W. (McGill Medical Undergraduate Journal, 1936)
Keywords: Médecine; Université McGill

Influence of the Edinburgh Medical School on the Early Development of McGill University - Ewing, Maurice (Journal canadien de chirurgie / Canadian Journal of Surgery, 1975)
Keywords: Médecine; Université McGill

La charité professionnelle: l'émergence de la carrière de travailleuse sociale à McGill (1913-1948) - Montour-Perras, Diane (Université du Québec à Montréal, 1988)
Keywords: Femmes; Université McGill

The History of Canadian Medical Schools, VIII: McGill University, Medical Faculty - Johnson, George R. (Calgary Associate Clinic Historical Bulletin, 1949)
Keywords: Médecine; Université McGill

La physique à McGill entre 1920 et 1940: la réception de la mécanique quantique par une communauté scientifique périphérique - Gingras, Yves (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 1991)
Keywords: Physique; Université McGill

A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2003)
Keywords: Chimie; Université McGill

'Archi-ettes' in Training: The Admission of Women to McGill's School of Architecture - Adams, Annmarie (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Femmes; Université McGill

Wisdom, Justice, and Charity: Canadian Social Welfare throught the life of Jane B. Wisdom, 1884-1975 - Morton, Suzanne (Studies in Gender and History, 2014)
Keywords: Philanthropie; Université McGill

Medical Genetics at McGill: The History of a Pioneering Research Group - Canning, Christopher; Weisz, George; Tone, Andrea; Cambrosio, Alberto (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2013)
Keywords: Médecine; Université McGill

The Stained Glass of the Hosmer Collection, McGill University - Bugslag, James; Isler-de-Jongh, Ariane (McGill-Queen's University Press, 2014)
Keywords: Université McGill; Vitraux

"An Ocean of Noise": H.E. Reilley and the Making of a Legitimate Social Problem, 1911-45 - Rudy, Jarrett; Kenny, Nicolas; Fahrni, Magda (Journal of Canadian Studies / Revue d'études canadiennes, 2017)
Keywords: Physique; Université McGill

Canada's big biblical bargain: how McGill University bought the Dead Sea Scrolls - Kalman, Jason; du Toit, Jaqueline Susann (McGill-Queen's University Press, 2010)
Keywords: Théologie; Université McGill

Many Women, Many Voices. Stories from McGill collections - Cooke, Nathalie; Giuliano, Frédéric; Lyons, Christopher; Owens, Gwendolyn; Sundberg, Jacquelyn; Yearl, Mary (Rare and Special Collections, Osler, Art, and Archives of McGill Library, 2018)
Keywords: Femmes; Université McGill

Looking Around: The Architecture of Medical Education - Adams, Annmarie (Transforming Medical Education: Historical Case Studies of Teaching, Learning, and Belonging in Medicine, 2022)
Keywords: Médecine; Université McGill

L’Office provincial des recherches scientifiques et le développement de la science au Québec, 1937-1960 - Almeida, Mike (Revue d'histoire de l'Amérique française, 2002)
Keywords: Université McGill; Université de Montréal

Les transformations des universités du XIIIe au XXIe siècle - Gingras, Yves; Roy, Lyse (Presses de l'Université du Québec, 2006)
Keywords: Université McGill; Université de Montréal

Émergence et évolution de la recherche en mathématiques au Québec, 1945-1984 - Foisy, Martine; Gingras, Yves (Société mathématique du Canada, 1945-1995. Vol. 1: Les mathématiques au Canada, 1995)
Keywords: Université McGill; Université de Montréal

L'institutionnalisation de la recherche en milieu universitaire et ses effets - Gingras, Yves (Sociologie et sociétés, 1991)
Keywords: Université McGill; Université de Montréal

John William Dawson: Faith, Hope, and Science - Sheets-Pyenson, Susan (McGill-Queen's University Press, 1996)
Keywords: Dawson, William; Université McGill

Sir William Peterson's Principalship, 1895-1919 - Collard, Edgar Andrew (McGill: The Story of a University, 1960)
Keywords: Peterson, William; Université McGill

Student Life at McGill: 1936-1940 - Lévesque, Andrée (Madeleine Parent: Activist, 2005)
Keywords: Parent, Madeleine; Université McGill

Leonard Marsh and the McGill Social Science Research Project - Irving, Allan (Journal of Canadian Studies / Revue d'études canadiennes, 1986)
Keywords: Marsh, Leonard; Université McGill

The First Fifty Years - Brittain, W. H. (Macdonald College of McGill University, The Next Fifty Years, 1955)
Keywords: Macdonald College; Université McGill

MacDonald College of McGill University; A History from 1904-1955 - Snell, John Ferguson (McGill University Press, 1963)
Keywords: Macdonald College; Université McGill

Macdonald College of McGill University, 1907-1988: A Profile of a Campus - Neilson, Helen R. (Coron Publishers, 1989)
Keywords: Macdonald College; Université McGill

The Beginning of Teacher Training at McGill University - Cooper, John Irwin (A Century of Teacher Education, 1857-1957, addresses delivered during the celebration of the century of the McGill Normal School, 1957)
Keywords: Enseignants; McGill Normal School; Université McGill

Impatient d’être soi-même. Les étudiants montréalais, 1895-1960 - Hébert, Karine (Presses de l'Université du Québec, 2008)
Keywords: Université McGill; Université de Montréal; Étudiants

From Tomorrow’s Elite to Young Intellectual Workers: The Search for Identity among Montreal Students, 1900-1958 - Hébert, Karine (Negotiating Identities in 19th and 20th Century Montreal, 2005)
Keywords: Université McGill; Université de Montréal; Étudiants

Between the Future and the Present: Montreal University Student Youth and the Post-War Years, 1945-1960 - Hébert, Karine (Cultures of Citizenship in Post-War Canada, 1940-1955, 2003)
Keywords: Université McGill; Université de Montréal; Étudiants

Introduction - Keating, Peter; Keel, Othmar (Santé et société au Québec: XIXe-XXe siècle, 1995)
Keywords: Médecine; Université McGill; Université de Montréal

La construction d'une identité étudiante montréalaise (1895-1960) - Hébert, Karine (Université du Québec à Montréal, 2002)
Keywords: Université McGill; Université de Montréal; Étudiants

The Early History of Medical Genetics in Canada - Leeming, William (Social History of Medecine, 2004)
Keywords: Médecine; Université McGill; Université de Montréal

De Freud au Père Mailloux : transmission, paradoxes et institutionnalisation : une histoire des origines de la psychanalyse au Québec - Adam-Vézina, Élodie (Université du Québec à Montréal, 2017)
Keywords: Psychologie; Université McGill; Université de Montréal

A Content Guide and Index to "The University Magazine", Vols. IX-XIX, 1910-1920 - Jones, Kim (Université Queen's, 1954)
Keywords: University Magazine (The); Université McGill

Attractions, curiosités, carnaval d'hiver, expositions agricoles et industrielles: le loisir public à Montréal au XIXe siècle - Dufresne, Sylvie (Montréal au XIXe siècle. Des gens, des idées, des arts, une ville, 1990)
Keywords: Carnaval; Expositions; Université McGill

Canadian Periodicals and Intellectual History: the Case of the McGill University Magazine / University Magazine, 1901-1920 - Mcnally, Peter F. (Cahiers de la Société bibliographique du Canada / Papers of the Bibliographical Society of Canada, 1980)
Keywords: University Magazine (The); Université McGill

The Man in the Ivory Tower: F. Cyril James of McGill - Frost, Stanley Brice (McGill-Queen's University Press, 1991)
Keywords: James, F. Cyril; Université McGill

La langue de la libération / The Language of Liberation - Mills, Sean (Des actions parlantes. Aspects de la culture québécoise des années 1960 et 1970 / Actions that speaks. Aspects of Quebec Culture in the 1960s and 1970s, 2012)
Keywords: Anglophones; Francophones; Université McGill

Le QI de Montréal. Quartier de l'innovation ou quartier imaginaire - Shearmur, Richard (Montréal : la cité des cités, 2017)
Keywords: Griffintown; Quartiers; Université McGill

Designing the Medical Museum - Adams, Annmarie (Healing Spaces, Modern Architecture, and the Body, 2018)
Keywords: Musées; Médecine; Université McGill

Des frontières culturelles en santé mentale au Canada? Entre psychiatrie, démographie et sociologie, retour sur les études de H.B.M. Murphy en épidémiologie - Delille, Emmanuel (Revue d'histoire de l'Amérique française, 2021)
Keywords: Médecine; Sociologie; Université McGill

« Who in hell are the McGill co-eds? A girls’ team you say? » : les enjeux reliés aux rapports genrés entourant le hockey féminin à McGill (1894—1941) - Scaire, Jérémy (Université de Montréal, 2024)
Keywords: Femmes; Hockey; Université McGill

University Club de Montréal - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Clubs; Patrimoine; Université McGill

Club Life / La Vie au Club - Robertson, Louise (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

Club Personalities / Les Personnalités du Club - MacKell, Peter R. D. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

The Club Building / L'Édifice du Club - Drummond, Derek A. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007 - MacKell, Peter R. D. (Price-Patterson Ltd, 2007)
Keywords: Clubs; University Club; Université McGill

The Beginning – The University Club in the Life of Montreal / Les débuts: Le Club universitaire au coeur de la vie Montréalaise - MacKell, Peter R. D. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; University Club; Université McGill

Carrie Derrick (1862-1941) and the Chair of Botany at McGill - Gillett, Margaret (Despite the Odds: Essays on Canadian Women and Science, 1990)
Keywords: Botanique; Derrick, Carrie; Université McGill

William Osler et la Bibliotheca Osleriana - Dumas, Paul (L'Union médicale du Canada, 1971)
Keywords: Médecine; Osler, William; Université McGill

The Osler Library - Gray, Charlotte (Journal de l'association médicale canadienne / Canadian Medical Association Journal, 1978)
Keywords: Bibliothèque Osler; Médecine; Université McGill

The Design of the Peter Redpath Museum at McGill University: the Genesis, Expression and Evolution of an Idea about Natural History - Bronson, Susan D. (Université de Montréal, 1992)
Keywords: Musées; Redpath (musée); Université McGill

Something Hidden: A Biography of Wilder Penfield - Lewis, Jefferson (Doubleday Canada, 1981)
Keywords: Médecine; Penfield, Wilder; Université McGill

Something Hidden: A Biography of Wilder Penfield - Lewis, Jefferson (Goodread Biographies, 1983)
Keywords: Médecine; Penfield, Wilder; Université McGill

Sir Thomas Roddick; His Work in Medecine and Public Life - Macdermot, Hugh E. (Macmillan, 1938)
Keywords: Médecine; Roddick, Thomas; Université McGill

Osler's Autopsies: their Nature and Utilization - Rodin, Alvin E. (Medical History, 1973)
Keywords: Médecine; Osler, William; Université McGill

The Life of Sir William Osler - Cushing, Harvey W. (Oxford University Press, 1940)
Keywords: Médecine; Osler, William; Université McGill

Sir William Osler: An Annotated Bibliography with Illustrations - Golden, Richard L.; Roland, Charles G. (Norman Pub., 1988)
Keywords: Médecine; Osler, William; Université McGill

Engineering Education and Research in Montreal: Social Constraints and Opportunities - Gingras, Yves; Gagnon, Robert (Minerva, 1988)
Keywords: Ingénieurs; Université McGill; École polytechnique

From Osler’s Library to the Osler Library of the History of Medicine, McGill University, Montreal: An Overview - Lyons, Christopher (Canadian Bulletin of Medical History, 2007)
Keywords: Bibliothèque Osler; Médecine; Université McGill

The Life of Sir William Osler - Cushing, Harvey W. (Clarendon Press, 1925)
Keywords: Médecine; Osler, William; Université McGill

The Design of the Peter Redpath Museum at McGill University: The Genesis, Expression, and Evolution of an Idea About Natural History - Bronson, Susan (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1992)
Keywords: Musées; Redpath (musée); Université McGill

Stones and Bones and Skeletons: the Origins and Developments of the Peter Redpath Museum, 1882-1912 - Sheets-Pyenson, Susan (McGill Journal of Education, 1982)
Keywords: Musées; Redpath (musée); Université McGill

Nobel pursuit. How Ernest Rutherford's Montreal research won the world's top science prize - Hardy, John (Canada's history, 2023)
Keywords: Brooks, Harriet; Physique; Université McGill

Histoire de la médecine au Québec, 1800-2000. De l'art de soigner à l'art de guérir - Goulet, Denis; Gagnon, Robert (Septentrion, 2014)
Keywords: Hôpitaux; Médecine; Université McGill; Université de Montréal

Faire l’économie du savoir. Usages et représentations du financement public des universités du Québec, de l’après-guerre à la Révolution tranquille (1950-1968) - Racine St-Jacques, Jules; Maltais, Martin (Globe: revue internationale d'études québécoises, 2014)
Keywords: Université McGill; Université Sir George Williams; Université de Montréal

John Stuart Foster, McGill University and the Renascence of Nuclear Physics in Montreal, 1935-1950 - Thomas, Jerry (Historical Studies in the Physical Sciences, 1984)
Keywords: Foster, John Stuart; Physique; Université McGill

Maude E. Abbott - Scriver, Jessie Boyd (The Clear Spirit, Twenty Canadian Women and Their Times, 1966)
Keywords: Abbott, Maude E.; Médecine; Université McGill

A Semicentennial Celebration. Introductory Address: A Sketch of the Life of the Late G.W. Campbell, A.M., M.D., L.L.D., Late Dean of the Medical Faculty, and a Summary of the History of the Faculty - Howard, R. P. (Gazette Printing, 1882)
Keywords: Campbell, George William; Médecine; Université McGill

A Biographical Sketch of the Late A.F. Holmes, M.D., LL.D., Including a Summary History of Medical Department of McGill College - Hall, Archibald (University Medical Students' Association of McGill College, 1860)
Keywords: Holmes, Andrew Fernando; Médecine; Université McGill

Andrew F. Holmes, M.D., LL.D., 1797-1860 - Abbott, M. E. (McGill University Magazine, 1905)
Keywords: Holmes, Andrew Fernando; Médecine; Université McGill

Anatomically Incorrect: Bodysnatching in the Nineteenth Century - Rankin, Matthew (The Beaver, 2002)
Keywords: Criminalité; Médecine; Université McGill; Étudiants

It Was a Man's World: Blaine Baker and the Writing of Canadian Legal History, 1981-2018 - Young, Brian (Law, Life, and the Teaching of Legal History. Essays in Honour of G. Blaine Bake, 2022)
Keywords: Ensiegnants; Histoire; Historiens; Université McGill

Un projet d’enquête sur la jeunesse universitaire (1913) - Trépanier, Charles (Les Cahiers des Dix, 2000)
Keywords: Groulx, Lionel; Université McGill; Université de Laval à Montréal

Technology and Two Cultures: One Hundred Years of Engineering Education in Montreal - Rabkin, Yakov M.; Levi-Lloyd, Ann (Minerva, 1984)
Keywords: Ingénieurs; Université McGill; Université de Montréal; École polytechnique

The Club Art Collection / La Collection d'oeuvres d'art du Club - Murphy, Sean B. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Peinture; University Club; Université McGill

Club Staff Over the Years / Le Personnel du Club au cours des années - MacKell, Peter R. D.; Armstrong, Julian (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Travail; University Club; Université McGill

La réception des rayons X au Québec: radiographie des pratiques scientifiques au Québec - Gingras, Yves (Sciences et médecine au Québec. Perspectives socio-historiques, 1987)
Keywords: Médecine; Physique; Technologie médicale; Université McGill

La Chambre des arts et manufactures: les quinze premières années (1857-1872) - Sabourin, Hélène (Université du Québec à Montréal, 1989)
Keywords: Board of Trade; Mechanics' Institute; Université McGill

La réception des rayons X au Québec: radiographie des pratiques scientifiques - Gingras, Yves (A New Kind of Ray: the Radiological Sciences in Canada - les Sciences radiologiques au Canada, 1895-1995, 1995)
Keywords: Médecine; Physique; Technologie médicale; Université McGill

The Life and Professional Contributions of Arthur Stanley Lamb, M.D., to Physical Education in Canada - Eaton, John Douglas (Ohio State University, 1964)
Keywords: Lamb, Arthur Stanley; Université McGill; Éducation physique

Opération McGill français - Warren, Jean-Philippe (Une douce anarchie. Les années 68 au Québec, 2008)
Keywords: Anglophones; Associations étudiantes; Francophones; Université McGill

Les cobayes oubliés: l'histoire du programme MK-ULTRA à Montréal - Blondin, Sophie-Andrée; Ellenwood, Lisa (Edito, 2024)
Keywords: Hôpitaux psychiatriques; Royal Victoria Hospital; Université McGill

Les étapes de la science économique au Québec: démarrage, construction et maturité - Fortin, Pierre (L'Actualité économique, 2000)
Keywords: Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal

Les relations culturelles du Québec avec la France, 1920-1965 - Roussel, Luc (Université Laval, 1983)
Keywords: Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal

Les ingénieurs sanitaires à Montréal, 1870-1945: lieux de formation et exercice de la profession - Gagnon, Robert; Zwarich, Natasha (Urban History Review / Revue d'histoire urbaine, 2008)
Keywords: Fonctionnaires; Ingénieurs; Université McGill; Université de Montréal; École polytechnique

Infrastructures urbaines et santé publique: l'émergence de la spécialisation du génie sanitaire à Montréal, 1892-1945 - Zwarich, Natasha (Université du Québec à Montréal, 2004)
Keywords: Fonctionnaires; Ingénieurs; Université McGill; Université de Montréal; École polytechnique

L'effet des dons des entreprises privées sur les organisations-non-productrices-de-profit: le cas des universités de Montréal - Fabi, Ian (Université de Montréal, 2010)
Keywords: Philanthropie; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal

L'émergence et le développement de la discipline informatique dans les universités québécoises (1960 à 2000) - Mirabel, Philippe (Université du Québec à Montréal, 2013)
Keywords: Anglophones; Francophones; Université McGill; Université de Montréal; Université du Québec à Montréal

The Science of Social Redemption. McGill, the Chicago School, and the Origins of Social Research in Canada - Shore, Marlene (University of Toronto Press, 1987)
Keywords: Dawson, Carl; Marsh, Leonard; Sociologie; Université McGill

Dans le mouvement étudiant à McGill - Lévesque, Andrée (Madeleine Parent, militante, 2003)
Keywords: Mouvement étudiant; Parent, Madeleine; Université McGill; Étudiants

The Heart of the Matter: Maude E. Abbott, 1869-1940 - Gillett, Margaret (Despite the Odds. Essays on Canadian Women and Science, 1990)
Keywords: Abbott, Maude E.; Femmes; Médecine; Université McGill

The Contributions of Wilder Penfield and the Montreal Neurological Institue to Canadian Neurosciences - Feindel, William (Health, Disease and Medecine. Essays in Canadian History, 1984)
Keywords: Institut neurologique; Médecine; Penfield, Wilder; Université McGill

L'institution royale et la fondation McGill - Audet, Louis-Philippe (La revue de l'Université Laval, 1952)
Keywords: Royal Institution for the Advancement of Learning; Université McGill

Eastern Gate and Western Cavalcade - a Commentory on the Part Played by Men of the Montreal General Hospital and McGill Medical School in the Early Medical History of Western Canada - Scarlett, E. P. (Canadian Services Medical Journal, 1956)
Keywords: Hôpitaux; Montreal General Hospital; Médecine; Université McGill

Andrew Fernando Holmes: Protestantism, Medicine, and Science in Nineteenth-Century Montreal - Vaudry, Richard W. (University of Toronto Press, 2020)
Keywords: Holmes, Andrew Fernando; Médecine; Protestants; Université McGill

An inner grace: the life story of Dr. Maude Abbott and the advent of heart surgery - Abbott, Elizabeth L. (2023)
Keywords: Abbott, Maude E.; Femmes; Médecine; Université McGill

Les hommes-relais de la bactériologie en territoire québécois et l’introduction de nouvelles pratiques diagnostiques et thérapeutiques (1890-1920) - Goulet, Denis; Keel, Othmar (Revue d'histoire de l'Amérique française, 1993)
Keywords: Hôpital Notre-Dame; Médecine; Université McGill; Université de Laval à Montréal; Université de Montréal

Origines géographiques et lieux de pratique des diplômés en médecine au Québec de 1834 à 1939 - Weisz, George (Sciences et médecine au Québec. Perspectives socio-historiques, 1987)
Keywords: Anglophones; Francophones; Médecine; Université McGill; Université de Montréal; École de médecine

L’enseignement de la médecine vétérinaire au Québec 150 ans d’histoire! - Pepin, Michel (Histoire Québec, 2016)
Keywords: McEachran, Duncan McNab; Université McGill; Université de Montréal; École de médecine vétérinaire

The Club and the Two World Wars / Le Club et les deux guerres mondiales - Claxton, John B. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Guerre; Poésie; University Club; Université McGill

Changing Times / Les temps changent - K. Paterson, Alex (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Femmes; Juifs; University Club; Université McGill

Getting a Job Done and Doing It Well: Dr. Blossom Wigdor, Psychologist and Gerontologist - Beaveridge, Janice (Despite The Odds: Essays on Canadian Women and Science, 1990)
Keywords: Femmes; Gérontologie; Psychologie; Université McGill; Wigdor, Blossom

The Abbotts of McGill - Frost, Stanley B. (McGill Journal of Education, 1973)
Keywords: Abbott, John; Abbott, Joseph; Abbott, Maude E.; Université McGill

Duncan McEachran 1841-1924 / Duncan McEachran 1841-1924 - Fulleringer, Pat (Héritage Dorval, 2003)
Keywords: McEachran, Duncan McNab; Université McGill; École de médecine vétérinaire

Wine and Food / Cuisine et vins - M. Romoff, Harvey (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Alcool; Alimentation; Clubs; Restaurant; University Club; Université McGill

Sir William C. Macdonald. A Biography - Fong, William (McGill-Queen's University Press, 2007)
Keywords: Macdonald College; Macdonald, William C.; Philanthropie; Tabac; Université McGill

The Gurds, the Montreal General and McGill: a family saga - Gurd, Fraser N. (General Store Publishing House, 1996)
Keywords: Hôpitaux; Montreal General Hospital; Médecine; Université McGill; École de médecine

L'opération McGill français. Une page méconnue de l'histoire de la gauche nationaliste - Warren, Jean-Philippe (Bulletin d'histoire politique, 2008)
Keywords: Anglophones; Associations étudiantes; Francophones; Groupes populaires; Université McGill; Université de Montréal; Université du Québec à Montréal

Rocke Robertson: surgeon and shepherd of change - Pound, Richard W. (McGill-Queen's University Press, 2008)
Keywords: Anglophones; Hôpitaux; Montreal General Hospital; Médecine; Université McGill; École de médecine

La Crise d'octobre et le milieu universitaire montréalais - Bédard, Éric (Université de Montréal, 1997)
Keywords: Crise d'octobre; Front de Libération du Québec; Université McGill; Université Sir George Williams; Université de Montréal; Université du Québec à Montréal; Étudiants

John Wilson McConnell. Homme d'affaires, éditeur de journal, humaniste et philanthrope canadien / John Wilson McConnell: Canadian businessman, newspaper publisher, humanitarian, and philanthropist - Nieuwendyk, Dick (Héritage Dorval, 2016)
Keywords: Hommes d'affaires; McConnell, John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

Déploiement et influence de l'Église catholique montréalaise - Perron, Normand (Histoire de Montréal et de sa région, 2012)
Keywords: Communautés religieuses; Diocèse; Institut canadien; Notre-Dame (paroisse); Sulpiciens; Ultramontains; Université McGill; Université de Laval à Montréal; Églises

The Spread and Influence of the Catholic Church in Montreal - Perron, Normand (Montreal: The History of A North American City, 2018)
Keywords: Communautés religieuses; Diocèse; Institut canadien; Notre-Dame (paroisse); Sulpiciens; Ultramontains; Université McGill; Université de Laval à Montréal; Églises

L’émeute des tramways de Montréal (1955) et la mauvaise conduite des étudiants: un cas d’appropriation de l’espace urbain - Poitras, Daniel (Urban History Review / Revue d'histoire urbaine, 2018)
Keywords: Association générale des étudiants de l'Université de Montréal; Associations étudiantes; Délinquance; Tramways; Transport en commun; Université McGill; Université de Montréal; Émeutes; Étudiants

Champ culturel et espace montréalais (I): la vie culturelle à Montréal avant 1960 - Bellavance, Guy; Poirier, Christian (Histoire de Montréal et de sa région, 2012)
Keywords: Art association; Expositions; Musique; Musée McCord; Musées; Radio; Théâtre; Université McGill; Édition

Cultural Field and Montreal Space (I): Cultural Life in Montreal - Bellavance, Guy; Poirier, Christian (Montreal: The History of A North American City, 2018)
Keywords: Art association; Expositions; Musique; Musée McCord; Musées; Radio; Théâtre; Université McGill; Édition

J.W. McConnell: Financier, Philanthropist, Patriot - Fong, William Jesse (McGill-Queen's University Press, 2008)
Keywords: Clubs; Hommes d'affaires; McConnell, John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

Encountering Maude Abbott - Adams, Annmarie (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2018)
Keywords: Abbott, Maude E.; Femmes; Histoire; Hôpitaux; Musées; Médecine; Royal Victoria Hospital; Université McGill

Nineteenth-Century Maps and Atlases of Montreal in the Collections of the Rare Book Department of the McGill University Library (Université McGill, 1973)
Keywords: Cartes et plans

The Changes in the Industrial Occupations of Women in the Environment of Montreal During the War Period, 1914-1918 - Price, Enid M. (Université McGill, 1919)
Keywords: Femmes; Guerre; Travail

Le livre d'orgue de Montréal: un premier regard sur la musique - Gilbert, Kenneth (L'orgue à notre époque, 1981)
Keywords: Musique

Un manuscrit inédit de musique d'orgue à Montréal au 18e siècle - Gallat-Morin, Élisabeth (L'orgue à notre époque, 1981)
Keywords: Musique

Prehistoric Montreal - Lighthall, W. D. (Université McGill, 1920)
Keywords: Archéologie; Autochtones; Dawson, William; Hochelaga; Lighthall, William Douw

Science et technologie à Montréal: la longue naissance d'une ville du savoir - Trépanier, Michel (Histoire de Montréal et de sa région, 2012)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin, Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

Science and Technology: The Coming of Age of a City of Knowledge - Trépanier, Michel (Montreal: The History of A North American City, 2018)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin, Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

Scolarisation, industrialisation et urbanisation au XIXe siècle - Gagnon, Robert (Histoire de Montréal et de sa région, 2012)
Keywords: Bureau des écoles protestantes; Commission des écoles catholiques de Montréal; Communautés religieuses; Enseignants; Université McGill; École normale Jacques-Cartier; École polytechnique; Écoles normales

Education in the Nineteenth Century - Gagnon, Robert (Montreal: The History of A North American City, 2018)
Keywords: Bureau des écoles protestantes; Commission des écoles catholiques de Montréal; Communautés religieuses; Enseignants; Université McGill; École normale Jacques-Cartier; École polytechnique; Écoles normales

Supplement to a Preliminary Guide to the Records of the Montreal General Hospital (School of Nursing) Deposited in the McGill University Archives, Accession no. 1501 (Archives de l'Université McGill, 1975)
Keywords: Hôpitaux; Montreal General Hospital

Supplement 4 and 5 to A Preliminary Guide to the Records of the Montreal General Hospital Deposited in the McGill University Archives, Accession No. 1501/417-466 - Noel, Marcellin (Archives de l'Université McGill, 1974)
Keywords: Hôpitaux; Montreal General Hospital

Supplement 3 to A Preliminary Guide to the Records of the Montreal General Hospital Deposited in the McGill University Archives, Accession No. 1501/200-416 - Noel, Marcellin (Archives de l'Université McGill, 1974)
Keywords: Hôpitaux; Montreal General Hospital

Abraham De Sola Papers: A Guide to the Microfilm - Miller, Evelyn (Archives de l'Université McGill, 1970)
Keywords: De Sola, Abraham; Juifs

The Segregated City: Class and Occupation in Montreal 1861-1901/La ville différenciée: professions et classes sociales à Montréal, 1861-1901 - Lewis, Robert D. (Université McGill, Département de géographie, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

An Analysis of the Payrolls of the Point St. Charles Shops of the Grand Trunk Railway - Hoskins, Ralph F. H. (Université McGill, Département de géographie, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

The Layered City: A Revolution in Housing in Mid-Nineteenth-Century Montreal - Hanna, David B. (Université McGill, Département de géographie, 1986)
Keywords: Logement

Infant Mortality in Montreal in 1860: The Roles of Culture, Class and Habitat - Thornton, Patricia; Olson, Sherry; Thach, Quoc Thuy (Université McGill, Département de géographie, 1987)
Keywords: Enfants; Mortalité

A Study of the Garrison Families in Montreal and Quebec City, 1855-1865 - Duchesne, André (Université McGill, Département de géographie, 1990)
Keywords: Famille; Garnison

Classe sociale et mobilité résidentielle: le cas des Irlandais à Montréal de 1851 à 1871 / Social Class and Residential Mobility, the Case of the Irish in Montreal 1851 to 1871 - Thach, Quoc Thuy (Université McGill, Département de géographie, 1985)
Keywords: Irlandais; Mobilité résidentielle

A City of Tenants: Home-Ownership and Social Class in Montreal, 1847-1881/Une ville de locataires : propriété résidentielle et classes sociales à Montréal de 1847 à 1881 - Hertzog, Stephen (Université McGill, Departement de géographie, 1985)
Keywords: Locataires; Logement

Supplement 2 to A Preliminary Guide to the Records of the Montreal General Hospital Deposited in the McGill University Archives, Accession Number 1501/174-199 - Andreassen, John C. L. (Archives de l'Université McGill, 1973)
Keywords: Hôpitaux; Montreal General Hospital

Supplement 1 to A Preliminary Guide to the Records of the Montreal General Hospital Deposited in the McGill University Archives, Accession No 1501/83 to 1501/173 - Andreassen, John C. L. (Archives de l'Université McGill, 1973)
Keywords: Hôpitaux; Montreal General Hospital

A Preliminary Guide to the Records of the Montreal General Hospital Deposited in McGill University Archives - Accession No 1501 - 1818-1972 - Andreassen, John C. L. (Archives de l'Université McGill, 1972)
Keywords: Hôpitaux; Montreal General Hospital

Occupations as Clues to Social Structure in Nineteenth-Century Montreal/Les professions indices de la structure sociale de Montréal, 1861 à 1901 - Olson, Sherry (Université McGill, Département de géographie, 1986)

The Tip of the Iceberg: Strategy for Research on Nineteenth-Century Montreal - Olson, Sherry (Université McGill, Département de géographie, 1986)

Les pierres de constructions m'ont raconté: une visite guidée de fossiles, roches et minéraux d'édifices montréalais - Birker, Ingrid; Kaylor, Joan; Gillingwater, Trevor (Musée Redpath et Université McGill, 2005)
Keywords: Géologie; Paléontologie

What building stones tell. A walking tour guide focusing on the fossils, rocks, and minerals of Montreal's buildings - Birker, Ingrid; Kaylor, Joan; Gillingwater, Trevor (Musée Redpath et Université McGill, 2002)
Keywords: Géologie; Paléontologie

Guide pour l'étude d'entreprises montréalaises et leurs archives avant 1947 / A Guide to the History and Records of Selected Montreal Business Before 1947 - Sweeny, Robert (Université McGill, Montreal Business History Project, 1979)

Understanding the Patterns of Language Use of Chinese Children in a Montreal Community School - Curdt-Christiansen, Xiao Lan (Université McGill, 1999)
Keywords: Chinois; Langue; Étudiants

Ukrainian Community Life in Montreal: Social Planning Implications - Tokar, Ann M. (Université McGill, 1992)
Keywords: Ukrainiens

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

The Young Men's Hebrew Association of Montreal: A Study of the Role of the Formal and Informal in an Ethnic Institution - Solomon, David N. (Université McGill, 1942)
Keywords: Juifs

The Well-Being of Kenyan-Canadian Parents and Youth Living in Mixed Families in Montreal - Williams, Alexandra (Université McGill, 2014)
Keywords: Africains; Famille

The Saint Patrick's Society of Montreal: Ethno-Religious Realignment in a Nineteenth-Century National Society - James, Kevin (Université McGill, 1997)
Keywords: Irlandais

The Role of The Gazette in Linguistic Group Relations in Quebec: A Contextual Approach - Ruvinsky, Ilene G. (Université McGill, 1984)
Keywords: Anglophones; Francophones; Montreal Gazette

The Refugee Youth Program in Montreal 1947-1952. A Descriptive and Analytical Study of the Integration of 40 Jewish Refugee Youths into the Montreal Community - Fischer, Greta; Switzer, Pearl (Université McGill, 1955)
Keywords: Enfants; Juifs

The Language Problem and School Board Reform on the Island of Montréal - Mackay, Murdo (Université McGill, 1987)
Keywords: Langue

The Greek Day School Socrates in Montreal: Its Development and Impact on Student Identity, Adjustment and Achievement - Bombas, Leonidas C. (Université McGill, 1988)
Keywords: Grecs

The Education of Italians in Montreal, 1895 to 1960 - Gadler, Yves Carmelo Luciano (Université McGill, 1994)
Keywords: Italiens

The Contributions of Montreal Holocaust Survivor Organizations to Jewish Communal Life - Giberovitch, Myra (Université McGill, 1988)
Keywords: Juifs

Sociolinguistic Features of Modern Greek as it is Spoken in Montreal - Maniakas, Theodoros (Université McGill, 1983)
Keywords: Grecs; Langue

Sri Lankan Women's Career Identity Evolution after Immigration to Montreal, Quebec, Canada - De Silva, Nilmini (Université McGill, 2010)
Keywords: Femmes; Sri Lankais; Travail

Shared Values, Different Paths: First-Generation Iranian Men's and Women's Perceptions of the Cultural Production of an "Educated Person" - Sadeghi, Shiva (Université McGill, 2004)
Keywords: Iraniens; Étudiants

Self-Identification Processes and their Reflection in the Language of Fourth-Wave Emigrants in Montreal - Migdissova, Svetlana (Université McGill, 2003)
Keywords: Langue; Russes

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Sankofa: Recovering Montreal’s Heterogeneous Black Print Serials - Williams, Dorothy W. (Université McGill, 2006)
Keywords: Noirs

Safeguarding Mother Tamil in Multicultural Quebec: Sri Lankan Legends, Canadian Myths, and the Politics of Culture - Brunger, Fern (Université McGill, 1994)
Keywords: Sri Lankais

Représentations culturelles et identité d'immigrants adultes de Montréal apprenant le français - Amireault, Valérie (Université McGill, 2007)
Keywords: Langue

Renegotiating Home and Identity: Experiences of Gujarati Immigrant Women in Suburban Montreal - Nair, Roopa (Université McGill, 1998)
Keywords: Femmes; Indiens

Private Rehabilitation in a Low Rent Area: Landlord-Tenant Relations and other Non-Market Factors - Duff, Huntly Douglas (Université McGill, 1973)
Keywords: Locataires; Logement; Portugais

Pressure Group Politics: Case Study of the St. Leonard Schools Crisis - Parisella, John E. (Université McGill, 1971)
Keywords: Italiens; Saint-Léonard (crise de)

L'insegnamento dell'italiano a Montreal verso il Duemila. Insegnamento e apprendimento al livello post-secondario in un contesto plurilingue - Picciano, Giovanna A. (Université McGill, 1997)
Keywords: Italiens; Langue

Entre globalisation et réalités locales: centres commerciaux et formes urbaines à Los Angeles, Montréal et Paris / Between Globalization and Local Realities: Shopping Centers and Urban Forms in Los Angeles, Montreal and Paris - Moretti, GianPiero (Université McGill, 2004)
Keywords: Centres commerciaux

Enforcing the Right to Healthy Housing: Recourse for Montreal Tenants Facing Health and Safety Problems at Home - Auchinleck, Jennifer (Université McGill, 2011)
Keywords: Locataires; Logement

Eating in the City: Diet and Provisioning in Early Nineteenth Century Montreal - Fyson, Donald William (Université McGill, 1989)
Keywords: Alimentation

Dufferin District: An Area in Transition - Robert, Percy A. (Université McGill, 1928)
Keywords: Quartiers; Saint-Laurent (quartier)

Die Geschichte des deutschsprachigen Theaters in Montreal von seinen Anfängen 1953 bis 1997 - Kremer, Johanna (Université McGill, 1998)
Keywords: Allemands; Théâtre

Deviance and Social Control among Haredi Adolescent Males - Levy, Jonathan (Université McGill, 2004)
Keywords: Juifs

Design Considerations in Urban Low-Income Housing Redevelopment with Special Reference to Montreal - Chan, David Wai (Université McGill, 1970)
Keywords: Logement

Des écoles à rendre communautaires - Lamarre, Jules (Université McGill, 1991)

Forging the Corporate Identity with Art: Four Montreal Corporations: Alcan Aluminium Limited, Martineau Walker, Banque Nationale du Canada, Loto-Quebec with a focus on Alcan - Meade, JoAnn (Université McGill, 2000)

Suspended Conversations: Private Photographic Albums in the Public Collection of the McCord Museum of Canadian History - Langford, Martha (Université McGill, 1997)
Keywords: Musée McCord; Musées; Photographie

Poésie et discours poétique au Canada français (1889-1909) - Campeau, Sylvain (Université McGill, 1999)
Keywords: Poésie

L’école littéraire de Montréal - Kieffer, Michael I. (Université McGill, 1939)
Keywords: École littéraire de Montréal

La critique littéraire au Québec en 1950: analyse de La Presse, Le Quartier latin, Le Devoir et Lectures - Deslierres, Deborah (Université McGill, 2005)
Keywords: Devoir (Le); Presse (La); Quartier latin (Le)

A History of Playwrights' Workshop Montreal, 1963-1988 - Curtis, Ron (Université McGill, 1991)
Keywords: Atelier de dramaturgie de Montréal (Playwrights' Workshop Montréal); Théâtre

Role-Playing Sociodramatic Simulations in the Montreal Area (1971-74) - Spiegel, Corinne (Université McGill, 1975)

Troubling Below: Rethinking Subcultural Theory - Stahl, Geoff (Université McGill, 1998)
Keywords: Musique

Word, Sound and Power: Rastafari and Conceptions of Musical Meaning in Roots Reggae Music - Macaulay, David E. (Université McGill, 1993)
Keywords: Musique

Accessibility: A Performance Measure for Land-Use and Transportation Planning in the Montréal Metropolitan Region - Cerdá, Assumpta (Université McGill, 2009)
Keywords: Navettage

Falling Up and Staying High: Commute Transit Mode Share Trends in Montreal Age Groups and Birth Cohorts - Grimsrud, Michael (Université McGill, 2013)
Keywords: Transport en commun

The (Spatialized) Hub-and-Spoke Industrial District Model: An Empirical Case Study of Montreal’s Aerospace Sector - Binkovitz, Isaac (Université McGill, 2009)
Keywords: Avionnerie

Industrial Land Retention in Two Cities: Municipal Strategies to Retain Manufacturing in Industrial Districts in Montreal and New York City - Charters, Stephen (Université McGill, 2011)
Keywords: Arrondissements; LaSalle; Le Sud-Ouest (arrondissement)

The Economics of Assembly and Transportation of Fluid Milk in the Montreal Area - Shipley, William Charlton (Université McGill, 1950)
Keywords: Lait

Modular Prefabrication versus Conventional Construction as a Cost Effective Alternative for the Construction of Single Family Detached Housing in the Montreal Area - Wiedemann, Stefan J. (Université McGill, 1990)
Keywords: Logement

Using E-Government to Strengthen Montreal's Chinese Ethnic Economy - Han, Yang (Université McGill, 2006)
Keywords: Chinois; Commerce de détail; Internet

The Development of Complex Commercial Projects in Central Areas with Special Reference to Montreal - Ng, Spencer Che Lou (Université McGill, 1965)
Keywords: Gratte-ciel

Inter-Urban Industrial Linkages in Montreal's Hinterland - Murricane, Kenneth (Université McGill, 1975)

Made in Montreal: A Study of Geography and Priorities of Small Urban Manufacturers in Post-Industrial Montreal - Carruthers, Alex (Université McGill, 2012)

La relation entre l'évolution du salaire réel et de l'emploi: Montréal, 1963-1982 - Dagenais, Vincent (Université McGill, 1990)

An Examination of Intra-Urban Mortality Patterns in Montreal: A Spatial Analytical Approach - Nisen, William George (Université McGill, 1977)
Keywords: Mortalité

Dispersal and Concentration of the Vietnamese Canadians: A Montreal Case Study - Lavoie, Caroline (Université McGill, 1988)
Keywords: Vietnamiens

Destination, Housing and Quality of Life in the Migrant Experience from Larino (Molise, Italy) to Milano and Montreal - Fainella, John G. (Université McGill, 1996)
Keywords: Italiens; Logement

For the Benefit of the Master: the Montreal Needle Trades During the Transition, 1820-1842 - Poutanen, Mary Anne (Université McGill, 1986)
Keywords: Apprentissage; Confection; Femmes

Édouard-Raymond Fabre, bourgeois patriote du Bas-Canada, 1799-1854 - Roy, Jean-Louis (Université McGill, 1972)
Keywords: Fabre, Édouard-Raymond; Librairie; Maires; Rébellions

An Index to Retail Market Prices in Montreal 1843-1867 - Horovitz, William Bela (Université McGill, 1967)
Keywords: Prix

The Application of Steam Navigation to the St. Lawrence 1809-1840 - Wilson, George H. (Université McGill, 1961)
Keywords: Navigation; Énergie hydraulique

The Montreal Ship Channel, 1805-1865 - Corley, Nora (Université McGill, 1961)
Keywords: Navigation

Internal Dynamics and the International Cycle: Questions of the Transition in Montreal, 1821-1828 - Sweeny, Robert (Université McGill, 1985)
Keywords: Artisans; Banque de Montréal; Banques; Bourgeoisie; Hommes d'affaires; Marchands

The Jewish Public Library of Montreal, 1914-1952 - Gubbay, Sharon Rachel (Université McGill, 1983)
Keywords: Jewish Public Library; Juifs

Reuben Brainin in Montreal (1912-1916) - Paz, Samuel (Université McGill, 1983)
Keywords: Brainin, Reuben; Juifs

Vivre comme frères: Native-French Alliances in the St Lawrence Valley, 1535-1667 - Cook, Peter (Université McGill, 2008)
Keywords: Autochtones; Français

A Fragile Authority: Power and the Religious Life in the Congrégation de Notre-Dame of Montreal, 1693-1796 - Gray, Colleen Allyn (Université McGill, 2004)
Keywords: Congrégation de Notre-Dame

Working for Family, Nation and God: Paternalism and the Dupuis Frères Department Store, Montreal, 1926-1952 - Matthews, Mary Catherine (Université McGill, 1997)
Keywords: Commerce de détail; Dupuis Frères; Magasins; Travail

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Domesticating Parks and Mastering Playgrounds: Sexuality, Power and Place in Montreal, 1870-1930 - Schmidt, Sarah (Université McGill, 1997)
Keywords: Délinquance; Mont-Royal (parc); Parcs; Places publiques

Residential Mobility in Montreal, 1861-1901 - Gilliland, Jason A. (Université McGill, 1993)
Keywords: Famille; Logement; Mobilité résidentielle

The Cholera Epidemic of 1832: State Formation and the Origins of the Montreal Board of Health - Sendzik, Walter (Université McGill, 1997)
Keywords: Choléra; Épidémies

Mothering Citizens: Elite Women in Montreal, 1890-1914 - Kirkland, Mary Elizabeth (Université McGill, 2012)
Cette thèse porte sur l'engagement social et politique de femmes de l'élite montréalaise de 1890 à 1914. Pour ce faire, j'ai réuni vingt Montréalaises issues des communautés anglophones, francophones, protestantes, catholiques et orthodoxes juives en une biographie collective qui lève le voile sur leur vie domestique, les rituels propres à leur classe sociale, leur travail philanthropique, de même que sur leur engagement au sein de la communauté locale et élargie. Cet exercice de style m'a permis de mettre en évidence l'influence des identités de genre, de race, d'ethnie, de classe et de religion de chacune sur sa conception de la société. La mise en commun des expériences de ces femmes de l'élite montréalaise révèle également que leurs préoccupations étaient plurielles et qu'elles dépassent la seule question du suffrage féminin. L'idéologie maternaliste embrassée par ces activistes traçait les jalons d'un futur meilleur, d'une ville assainie et d'une nation plus forte. Ma thèse est que les femmes constituant ce corpus combinaient leurs rôles de mères et leurs identités de citoyennes afin de se tailler une place, un cercle d'influence, dans des sphères d'activité qui leurs étaient habituellement défendues, soit les sphères sociale et politique. Pour y arriver, elles ont placé la famille au cœur de leur conception du système social et ont transposé cette vision à la communauté, à la nation et au monde. En tant qu'épouses, mères, mais aussi en tant que citoyennes, ces maternalistes croyaient qu'elles avaient un rôle important à jouer dans la transformation de la société. Le fait qu'elles aient partagé les mêmes identités sexuelle et sociale leur a permis de se rapprocher. Ces similarités, jumelées à leurs différences ethniques et religieuses leurs ont conféré une influence et un pouvoir indéniable à Montréal et au-delà. Les sources consultées révèlent que ces femmes de l'élite montréalaise étaient loin d'être passives ou contentes de rester dans l'ombre. Leur engagement politique et citoyen était conscient. Leur influence comportait néanmoins des limites qu'elles durent apprendre à repousser avec doigté. Avec le déclenchement de la Grande Guerre, les tensions cachées qui existaient entre elles s'aggravèrent et il ne fut bientôt plus possible de coopérer. La séparation de ce groupe eut pour résultat de diminuer de façon notoire le pouvoir et l'influence que ces femmes de l'élite montréalaise avaient acquis en près de vingt-cinq ans.
Keywords: Bourgeoisie; Femmes

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

Narratives and Identities in the Saint Lawrence Valley, 1667-1720 - Gray, Linda Breuer (Université McGill, 1999)

Le personnage de Julie Bruneau dans la correspondance de Papineau - Arbach, Marla (Université McGill, 2001)
Keywords: Papineau, Louis-Joseph

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

Le rôle des déterminismes sociaux dans le développement des forces productives de l'industrie textile du Canada, 1870 à 1910 - Ferland, Jacques (Université McGill, 1982)
Keywords: Textile

Spatial Aspects of Real Estate Transactions an Exploratory Study of the Island of Montreal: 1947-1967 - De Jong, Nicolas J. (Université McGill, 1971)

In Quest of Emotional Gratification and Cognitive Consonance: Organized Labour and Québec Separatist Nationalism, 1960-1980 - Güntzel, Ralph Peter (Université McGill, 1997)
Keywords: Nationalisme; Travail

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

W.D. Lighthall: Sometime Confederation Poet, Sometime Urban Reformer - Wright, Donald A. (Université McGill, 1991)
Keywords: Lighthall, William Douw; Réformistes; Écrivains

The Confédération des syndicats nationaux, the Idea of Independence, and the Sovereigntist Movement, 1960-1980 - Güntzel, Ralph Peter (Université McGill, 1991)
Keywords: Confédération des syndicats nationaux; Nationalisme

Cyclist Injury Risk and Pollution Exposure at Urban Signalized Intersections - Strauss, Jillian (Université McGill, 2012)
Keywords: Cyclisme; Pollution

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

La motorisation ou "La rançon du progrès". Tramways, véhicules-moteurs et circulation (Montréal, 1900-1930) - Veilleux, Denis (Université McGill, 1998)
Keywords: Automobile; Tramways; Transport en commun

Long-Term Results of User Participation in Housing Rehabilitation: The Community Design Workshop in Pointe St. Charles - You, Danhui (Université McGill, 1998)
Keywords: Logement; Pointe-Saint-Charles

Intersecting Discourses: Deaf Institutions and Communities in Montreal, 1850-1920 - Perreault, Stéphane- D (Université McGill, 2003)
Keywords: Clercs de Saint-Viateur; Communautés religieuses; Institution des sourdes-muettes; Institution des sourds-muets; Soeurs de la Providence; Sourds

Les aubergistes et les cabaretiers à Montréal en 1700 - Poliquin, Marie-Claude (Université McGill, 1996)
Keywords: Auberges

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

The Montreal Repertory Theatre, 1930-1961: a History and Handlist of Productions - Booth, Philip (Université McGill, 1989)
Keywords: Théâtre

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Menstruation Goes Public: Aspects of Women's Menstrual Experience in Montreal, 1920-1975 - Armeni, Elizabeth (Université McGill, 1996)
Keywords: Femmes

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

St. Lawrence Blvd. as "Third City": Place, Gender and Difference along Montréal's "Main" - Podmore, Julie (Université McGill, 1999)
Keywords: Rues; Saint-Laurent (rue)

L'éducation "idéale" dans un monde "idéal": le Dunham Ladies' College / St. Helen's School et l'élite anglicane du diocèse de Montréal (1870-1930) - Harbec, Marie-Ève (Université McGill, 2001)
Keywords: Anglicans

Organized Righteousness Against Organized Viciousness: Constructing Prostitution in Post World War I Montreal - Herland, Karen (Université McGill, 2005)
Keywords: Prostitution

Women in Montreal during Three Wars: an Examination of Gender, Nationalism and Colonialism - Pickles, Katie (Université McGill, 1996)
Keywords: Femmes; Guerre; Nationalisme

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

Women and Political Participation: the Montreal Citizens Movement, 1974-1989 - Van der Veen, Paula Louise (Université McGill, 1990)
Keywords: Femmes; Rassemblement des citoyens et citoyennes de Montréal

Salubrious Settings and Fortunate Families: The Making of the Golden Square Mile, 1840-1895 - MacLeod, Roderick (Université McGill, 1998)
Keywords: Anglophones; Golden Square Mile; Protestants; Quartiers

Mobilizing Canada: the National Resources Mobilization Act, the Department of National Defence, and Compulsory Military Service in Canada - Byers, Daniel Thomas (Université McGill, 2000)
Keywords: Conscription; Guerre

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Collective Memory and Diasporic Articulations of Imagined Homes: Armenian Community Centres in Montreal - Manjikian, Lalai (Université McGill, 2005)
Keywords: Arméniens

'Justice in the Premises': Family Violence and the Law in Montreal, 1825-1850 - Pilarczyk, Ian C. (Université McGill, 2003)
Keywords: Criminalité; Droit; Enfants; Famille

The Kahnawake Iroquois and the Lower-Canadian Rebellions, 1837-1838 - Sossoyan, Matthieu (Université McGill, 1999)
Keywords: Autochtones; Iroquois; Rébellions

Images and Reality of Fatherhood: a Case Study of Montreal's Protestant Middle Class, 1870-1914 - Fish, Cynthia (Université McGill, 1992)
Keywords: Famille; Protestants

A History of Mackay School for the Deaf - Hawthorn, Lorna Helen (Université McGill, 1960)
Keywords: Mackay School for the Deaf; Mackay, Joseph; Sourds

Immigrant Perceptions of Canadian schools: a Study of Greek Parents in Montréal - Shore, Bettina (Université McGill, 1979)
Keywords: Grecs

City at War: The Effects of the Second World War on Verdun, Québec - Durflinger, Serge Marc (Université McGill, 1997)
Keywords: Guerre; Quartiers; Verdun

Leisure Facilities in Montreal 1970 - Acosta, Carlos A. (Université McGill, 1972)

Salsa and its Transnational Moves: The Commodification of Latin Dance in Montreal - Pietrobruno, Sheenagh (Université McGill, 2001)
Keywords: Danse

The Movement for Public Housing in Montreal, 1930-1958 - Ruddick, Susan M. (Université McGill, 1979)
Keywords: Logement

The First Years of Medical Practice: A Study of the Initiation of Medical Practice by Fifty-Two Montreal Jewish Physicians Graduated Since 1940 - Loeb, Bernice Peritz (Université McGill, 1959)
Keywords: Hôpital général juif; Hôpitaux; Juifs; Médecine

The Montreal Maternity, 1843-1926: Evolution of a Hospital - Kenneally, Rhona (Université McGill, 1983)
Keywords: Hôpitaux; Montreal Maternity Hospital

Metropolitan Reform in Montreal - Baril, Paul-André (Université McGill, 1980)
Keywords: Communauté urbaine

The Genesis of the Montreal Council of Social Agencies - Shepard, W. C. (Université McGill, 1957)
Keywords: Montreal Council of Social Agencies

Charity and Change: the Montreal Council of Social Agencies' Attempts to Deal with the Depression - Maclennan, Anne Frances (Université McGill, 1984)
Keywords: Crise; Montreal Council of Social Agencies

A History of the Society for the Protection of Women and Children in Montreal - Douglas, Muriel H. (Université McGill, 1967)
Keywords: Enfants; Femmes; Society for the Protection of Women and Children

Les chansons de "La Bolduc": manifestation de la culture populaire à Montréal (1928-1940) - Leclerc, Monique (Université McGill, 1974)
Keywords: Bolduc, La; Chanson

Le théâtre français à Montréal, 1878-1931 - Bisson, Margaret M. (Université McGill, 1931)
Keywords: Théâtre

The Segregated City: Residential Differentiation, Rent and Income in Montreal, 1861-1901 - Lewis, Robert D. (Université McGill, 1985)
Keywords: Locataires; Logement; Mobilité résidentielle

The Montreal Chinese Hospital 1918-1982: A Case Study of an Ethnic Institution - Ho, Kwong-Ming (Université McGill, 1984)
Keywords: Chinois; Hôpital chinois; Hôpitaux

The Presbyterian College Montreal, 1865-1915 - Johnston, John A. (Université McGill, 1951)
Keywords: Presbyterian College; Presbytériens; Protestants

The High School for Girls, Montreal 1875-1914 - Burdett, Gillian Mary (Université McGill, 1963)
Keywords: Femmes; High School for Girls

The View From the Classroom: English Schoolteachers' Responses to Domestic and International Problems of the Interwar Years, 1919-1939 - Bregman, Abigail Sibley (Université McGill, 1986)
Keywords: Anglophones; Enseignants

The Role of the Black Community in Educating Blacks in Montreal, from 1910 to 1940, with Special Reference to Reverend Dr Charles Humphrey Este - Bertley, June A (Université McGill, 1982)
Keywords: Este, Charles Humphrey; Noirs

The Organization of Production and the Heterogeneity of the Working Class: Occupation, Gender and Ethnicity among Clothing Workers in Quebec - Teal, Gregory L. (Université McGill, 1986)
Keywords: Confection; Femmes; Juifs; Vêtements

The Ethnic Division of Labour in Montreal, 1931-1951 - Rennie, Douglas Lloyd (Université McGill, 1953)

A Study of the Point St. Charles Shops of the Grand Trunk Railway in Montreal, 1880-1917 - Hoskins, Ralph F. H. (Université McGill, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

Evolution des rapports sociaux dans l'industrie canadienne du cuir au tournant du 20e siècle - Ferland, Jacques (Université McGill, 1986)
Keywords: Chaussure

The Locomotive Engineers' Strike on the Grand Trunk Railway in 1876-1877 - Ayers, Shirley Anne (Université McGill, 1961)
Keywords: Chemins de fer; Grand Tronc; Ingénieurs

Some Aspects of Residential Mobility in Urban Social Space - Gilmour, Gillian M. (Université McGill, 1969)
Keywords: Logement; Mobilité résidentielle

The Social Adjustment of British Immigrant Families in Verdun and Pointe-Saint-Charles - Davidson, Mary (Université McGill, 1933)
Keywords: Britanniques; Pointe-Saint-Charles; Quartiers; Verdun

A Profile of Moroccan Jewish Immigration in Montreal 1957-1967 - Berman, Gerald (Université McGill, 1970)
Keywords: Juifs; Maghrébins; Marocains

Spatial Patterns of Selected Retail Activities, Montreal 1950-1970 - Bouchard, Diana C. (Université McGill, 1972)
Keywords: Commerce de détail

The Port of Montreal - Tombs, Laurence Chalmers (Université McGill, 1926)
Keywords: Port

The Impact of the St. Lawrence Seaway on the Port of Montreal - Slack, Brian (Université McGill, 1963)
Keywords: Navigation; Port; Voie maritime

Housing in the Suburban Region of Montreal, 1951-1961 - Dernoi, Louis Anthony (Université McGill, 1964)
Keywords: Banlieue; Logement

Montreal, a City Built by Small Builders, 1867-1880 - Hanna, David B. (Université McGill, 1987)
Keywords: Logement

Spatial Aspects of Real Estate Transactions: An Exploratory Study of the Island of Montreal, 1947-1967 - Dejong, Nicolas J. (Université McGill, 1971)

The Sun Life Insurance Company of Montreal, 1872-1900 - Pollack, Gladys (Université McGill, 1980)
Keywords: Assurance; Sun Life Assurance

History and Organisation of the Montreal Stock Exchange - Johnson, J. S. (Université McGill, 1934)
Keywords: Bourse

The Montreal Garment Industry, 1871-1901 - Payette-Daoust, Michelle (Université McGill, 1986)
Keywords: Confection

Industrial Location in the City of St. Laurent - Isenberg, Seymour (Université McGill, 1967)
Keywords: Saint-Laurent (ville)

Montreal Regional Industrial Pattern as Compared to that of Toronto - Fisher, David (Université McGill, 1940)

Montreal Chinese Property Ownership and Occupational Change, 1881-1981 - Aiken, Rebecca Bruff (Université McGill, 1985)
Keywords: Chinois; Travail

The French and English Social Elites in Montreal - Ross, Eileen (Université McGill, 1941)
Keywords: Anglophones; Francophones

Social Mobility in the Home-Building Industry in Montreal, 1951-1961 - Rawin, Solomon John (Université McGill, 1962)
Keywords: Logement

The Irish Migration to Montreal, 1847-1867 - Keep, George Rex (Université McGill, 1948)
Keywords: Irlandais

Socio-Spatial Patterns of Infant Survival in Montreal, 1859-1860 - Thach, Quoc Thuy (Université McGill, 1987)
Keywords: Enfants; Mortalité

The First Fifteen Years of British Administration in Montreal, 1760 to 1775 - Dewey, Alex G. (Université McGill, 1913)
Keywords: Britanniques

The Irish in Montreal, 1867-1896 - Cross, D. Suzanne (Université McGill, 1969)
Keywords: Irlandais

Occupational Mobility and Achievements of Post-War Chinese Immigrants in Montreal - Chiang, Frances Shiu-Ching (Université McGill, 1978)
Keywords: Chinois; Travail

The Slovakian Community in Montreal - Brown, Wilfrid Harold (Université McGill, 1927)
Keywords: Slovaques

The American Presbyterian Church of Montreal, 1822-1866 - Knowles, David Clifford (Université McGill, 1957)
Keywords: American Presbyterian Church; Presbytériens; Protestants

Farm Leases and Agriculture on the Island of Montreal, 1780-1820 - Waywell, Jennifer L. (Université McGill, 1989)
Keywords: Baux à ferme; Notaires

A Stake in the System: Domestic Property Ownership and Social Class in Montreal, 1847-1881 - Hertzog, Stephen (Université McGill, 1984)
Keywords: Logement

La Banque du Peuple, 1835-1871, and its Failure, 1895 - Greenfield, Robert S. (Université McGill, 1968)
Keywords: Banque du Peuple; Banques

A History of St. John's School and Lower Canada College - Caverhill, Austin (Université McGill, 1961)
Keywords: Lower Canada College; St. John's School

The Legal Rights of Masters, Mistresses and Domestic Servants in Montreal, 1816-1829 - Hogg, Grace Laing (Université McGill, 1989)
Keywords: Domestiques; Femmes

History of the Theatre in Montreal Prior to the Confederation - Conroy, Patricia (Université McGill, 1936)
Keywords: Théâtre

The Civil Architecture of John Ostell - James, Ellen S. (Université McGill, 1983)
Keywords: Arpenteurs; Ostell, John

The Montreal Villa, 1830 to 1930 - Jooste, Johan K. (Université McGill, 1985)

An Imperial Garrison in its Colonial Setting. British Regulars in Montreal, 1832-1854 - Senior, Elinor Kyte (Université McGill, 1976)
Keywords: Armée; Britanniques; Garnison

The Annexation Movement of 1849-50 as Seen through the Lower Canadian Press - Mills, G. H. S. (Université McGill, 1947)
Keywords: Avenir (L'); Minerve (La); Montreal Gazette; Mouvement annexionniste

The First Incorporation of the City of Montreal, 1826-1836 - Ste Croix, Lorne (Université McGill, 1971)

Paupérisme et assistance sociale à Montréal 1832-1865 - Lapointe-Roy, Huguette (Université McGill, 1972)
Keywords: Pauvreté

Abandoned Children in Nineteenth-Century Montreal - Gossage, Peter (Université McGill, 1984)
Keywords: Communautés religieuses; Crèche d'Youville; Enfants; Orphelinats; Soeurs Grises

L'Institut canadien de Montréal 1844-1883: le contenu littéraire de la bibliothèque - Lebeau, Armande (Université McGill, 1981)
Keywords: Institut canadien

Early Canadian Historical Literature: The Journal of the Traders of the North West Co. Of Merchants from Canada - O'Brien, M. V. (Université McGill, 1957)
Keywords: Compagnie du Nord-Ouest; Fourrure; Marchands

Montreal's Musical Life Under the Union, with an Emphasis on the Terminal Years, 1841 and 1867 - Slemon, Peter (Université McGill, 1976)
Keywords: Musique

The Evolution of Montreal's Precipitation: Climate - Leduc, Richard (Université McGill, 1977)
Keywords: Climat

The Occupational Adjustments of Montreal Negroes, 1941-1948 - Potter, Harold Herbert (Université McGill, 1949)
Keywords: Noirs

The Development and Social Adjustment of the Jewish Community in Montreal - Seidel, Judith (Université McGill, 1939)
Keywords: Juifs

The Montreal Negro Community - Israel, Wilfrid Emerson (Université McGill, 1928)
Keywords: Noirs

The Social Structure of the Italian and Ukrainian Communities in Montreal, 1935-1937 - Bayley, Charles M. (Université McGill, 1939)
Keywords: Italiens; Ukrainiens

Political Power and Urban Redevelopment: A Case Study of Montreal - Kardos, Robert (Université McGill, 1969)
Keywords: Logement; Petite-Bourgogne

The Attitudes of the Montreal Jewish Community toward French Nationalism and Separatism - Coleman, Romalis (Université McGill, 1967)
Keywords: Francophones; Juifs; Nationalisme

Development of High-Rise Habitation in Central Urban Areas with Special Reference to Montreal - Raina, S. K. (Université McGill, 1974)
Keywords: Logement

L'éducation dans le diocèse de Montréal d'après la correspondance de ses deux premiers évêques, Mgr J.-J. Lartigue et Mgr I. Bourget, de 1820 à 1867 - Majerus, Yvette-Viviane (Université McGill, 1971)
Keywords: Bourget, Ignace; Lartigue, Jean-Jacques; Évêques

Mgr Édouard-Charles Fabre et le diocèse de Montréal. La question d'un coadjucateur à l'évêque de Montréal (1872-1873) et la question de l'érection de Montréal en archevêché (1879-1887): aperçu des relations interépiscopales - Jolin, Jean-Pierre (Université McGill, 1972)
Keywords: Diocèse; Fabre, Édouard-Charles; Évêques

The Egyptians in Montreal: A New Color in the Canadian Ethnic Mosaïc - Wassef, Nadia Hanna (Université McGill, 1978)
Keywords: Égyptiens

A Recreational Hinterland Comparison between Montréal and Québec City - Secondi, Bruno (Université McGill, 1990)

The Physical Characteristics of Suburban Development with Special Reference to the Lakeshore Communities of Montreal - Gibbs, Phillip F. (Université McGill, 1971)
Keywords: Banlieue; West Island

The Evolution of Commercial Land Use in Cities, with Special Reference to Montreal - Auyang, Antonio Chak War (Université McGill, 1965)

Street Patterns in Residential Areas with Special Reference to Montreal - Li, Ying H. (Université McGill, 1965)
Keywords: Rues

A Study of the Relationship between Ecological and Non-Ecological Factors in the Development of Certain Natural Areas of Montreal - Richardson, Nigel H. (Université McGill, 1954)
Keywords: Notre-Dame-de-Grâce; Quartiers; Rosemont; Snowdon

Vocational Training Facilities for Women in Montreal - Boulkind, Mabel (Université McGill, 1938)
Keywords: Enseignement professionnel; Femmes

The Economic and Social Adjustment of Slavic Immigrants in Canada with Special Reference to the Ukrainian of Montreal - Mamchur, Stephen (Université McGill, 1935)
Keywords: Ukrainiens

Ukrainian Bilingual Education in the Montreal Public School System, 1911-1945 - Melnyk, Iryna (Université McGill, 1987)
Keywords: Ukrainiens

The Occupational Adjustment of the British Immigrant in Montreal - Reynolds, Lloyd George (Université McGill, 1933)
Keywords: Britanniques

The Construction Industry in Montreal with Special Reference to Seasonal Unemployment - Berman, Alfred (Université McGill, 1931)
Keywords: Chômage

Changes in the Intra-Urban Land-Value Surface: The Impact of Transportation, Land-Use and Socio-Economic Factors in Central Montreal - Foggin, Peter M. (Université McGill, 1970)

The Lachine Canal - Cureton, Edward A. (Université McGill, 1957)
Keywords: Lachine (canal); Navigation

The Relationship between Landscape and Residential Growth Patterns: The Example of Western Montreal Island - Bridger, M. Keith (Université McGill, 1964)
Keywords: West Island

The Social Adjustment of Hungarian Refugees in Montréal - Gellert, Judith (Université McGill, 1964)
Keywords: Hongrois

Evolution of Patterns of Land Subdivision with Special Reference to Montreal - Khor, Ean (Université McGill, 1964)

The Construction of the First Lachine Canal, 1815-1826 - Tulchinsky, Gerald (Université McGill, 1960)
Keywords: Lachine (canal); Navigation

City Squares and Open Spaces with Special Reference to Montreal - Hoffman, Andrew (Université McGill, 1962)
Keywords: Places publiques; Squares

Les troupes de la marine, 1683-1713 - Russ, Christopher John (Université McGill, 1971)
Keywords: Armée

Housing of Female Single-Parent Families with Special Reference to Point St. Charles - Bourianova, Ioulia (Université McGill, 1996)
Keywords: Femmes; Logement; Pointe-Saint-Charles; Quartiers

The Evolution of Montreal’s Cemetery Space from 1642 to the Present - Mappin, Charles (Université McGill, 1995)
Keywords: Cimetières

Making and Using Environmental Information: An Analysis of the Development and Use of Two GIS Tools for Public Environmental Engagement - Klinsky, Sonja (Université McGill, 2004)
Keywords: West Island

Transition of Asylum Seekers from Shelters to Independent Living - Balyejjusa, Moses Senkosi (Université McGill, 2009)

Montreal Up in Smoke: A Spatial Analysis of Mid-Nineteenth Century Urban Fires - Spencer, Pheobe (Université McGill, 2011)
Keywords: Incendies

Madame James McGill (1747-1818): Marie-Charlotte Guillimin, ou, La vie d'une femme mondaine à Montréal au dix-huitième siècle - Tanguay, Lynda (Université McGill, 1993)
Keywords: Bourgeoisie; McGill, James

The Law of Servants and the Servants of the Law: Judicial Regulation of Labour Relations in Montreal, 1830-1845 - Pilarczyk, Ian C. (Université McGill, 1997)
Keywords: Droit; Travail

"To Be Sold, a Negro Wench": Slave Ads of the Montreal Gazette, 1785-1805 - Extian-Babiuk, Tamara (Université McGill, 2006)
Keywords: Esclaves; Montreal Gazette; Noirs

Dependency among British Immigrants in Montreal - Ramsden, Mary Ellen (Université McGill, 1933)
Keywords: Britanniques

Refugee Narratives in Montreal: Negotiating Everyday Social Exclusion and Inclusion - Manjikian, Lalai (Université McGill, 2014)
Keywords: Théâtre

The Economic Adjustment of North African Jewish Immigrants in Montreal - Moldofsky, Naomi (Université McGill, 1968)
Keywords: Juifs; Maghrébins

A Logic of Ethnicity: A Study of the Significance and Classification of Ethnic Identity among Montréal Portuguese - Fernandez, Ronald (Université McGill, 1977)
Keywords: Portugais

The Japanese in Montreal: Socio-Economic Integration and Ethnic Identification of an Immigrant Group - Keiko, Minai (Université McGill, 1977)
Keywords: Japonais

Your Roots Will Be Here, Away from your Home: Migration of Greek Women to Montreal 1950-1980 - Dounia, Margarita (Université McGill, 2004)
Keywords: Femmes; Grecs

Effects of Migration on Alcohol Use: A Survey of Drinking Patterns, Attitudes and Alcohol-Related Problems among Ecuadorians in Ecuador and in Montreal - Vega Mansilla, Gustavo (Université McGill, 1982)
Keywords: Alcool; Équatoriens

A Study of the Academic Achievement and Personal and Social Adjustment of Jewish Moroccan Immigrant Students in the English High Schools of Montreal - Godfrey, Marvin Julian (Université McGill, 1970)
Keywords: Juifs; Maghrébins; Marocains

Montreal Anglophones: Social Distance and Emigration - Lange, Mélanie (Université McGill, 1985)
Keywords: Anglophones

Socio-Cultural Factors Affecting the Language Learning Experiences of South Asian Female Immigrants - Steinbach, Marilyn (Université McGill, 1998)
Keywords: Bengalis; Femmes; Indiens; Langue; Pakistanais; Sri Lankais

Where Do I Belong? Narratives from the Lives of Iranians in Montreal - Dehghani Estarki, Mahdi (Université McGill, 2010)
Keywords: Iraniens

The Means and Modes of Living of European Immigrants in Montreal - Gibbard, Harold A. (Université McGill, 1934)
Keywords: Finlandais; Italiens

Migrant Domestic Workers in Montreal: An Exploratory Study - Motta, Madeleine Marie (Université McGill, 1977)
Keywords: Domestiques

Privacy in Homes of Shaamy Muslim Immigrants: A Study of Privacy Patterns in Single-Family Detached Homes and Townhouses of Middle-Class Immigrants in Montreal - Hallak, Mahmoud Essam (Université McGill, 2000)
Keywords: Musulmans; Syriens

Effect of Premigratory Exposure to Political Violence on the Social Anchorage of Refugees in Montreal - Drapeau, Aline (Université McGill, 2001)

Rethinking Juvenile Prostitution: Insights from Youths on the Street - Morris, Jason (Université McGill, 1999)
Keywords: Enfants; Prostitution

The Natural Areas of the Montreal Metropolitan Community with Special Reference to the Central Area - Zatuka, Leo (Université McGill, 1948)
Keywords: Parcs

Dietary Outcomes of a School-Based Trial to Reduce Risk Factors for Coronary Heart Disease - Esslinger, Krista (Université McGill, 2000)
Keywords: Alimentation; Diététique

Patterns of Living of Elderly People in Montreal. A Study of the Patterns of Living of 137 People 70 Years of Age and Over Who "Live in Three Different Socio-Economic Areas in Montreal - Adefrissew, Demissie; Cooperberg, Arlene; Driedger, Florence; Driedger, Otto; Ferguson, Janet; Gerima, Yohannes W.; Sims, Valerie; Weinstein, Herbert; Zukerman, Harold (Université McGill, 1958)

The Convalescent Care of Children in Montreal - Fraser, Mary Constance (Université McGill, 1951)
Keywords: Children's Memorial Hospital; Enfants; Hôpital Notre-Dame; Hôpital Sainte-Justine; Hôpital général juif; Hôpitaux; Royal Victoria Hospital; St. Mary's Hospital

Career Contingencies of English-Montreal Physicians - Cook, H. George (Université McGill, 1969)
Keywords: Hôpitaux; Médecine

The French-Canadian Doctor in Montreal: A Study of Careers in a Profession - Brazeau, Jacques (Université McGill, 1951)
Keywords: Médecine

Providing a Home and then Some: A study of Montreal's Homeownership Programme - Pinches, Brendan James (Université McGill, 2010)
Keywords: Logement

Climate Change Adaptation and Mitigation through Urban Agriculture: A Montreal Case Study - Lebedeva, Julia (Université McGill, 2008)
Keywords: Climat

Loft Conversions in a Local Context: The Case of Inner City Montreal - Podmore, Julie (Université McGill, 1994)
Keywords: Logement

Housing without Families: The Housing Situation of Non-Family Households in Montreal - Lavigne, Jean-François (Université McGill, 1988)
Keywords: Logement

Community Response to Environmental Change: A Case Study of Montreal's West Island 1981-1991 - Adams, Jennifer (Université McGill, 1992)
Keywords: Quartiers; West Island

Residential Rehabilitation - with Special Reference to Montreal - Santiago, Arturo M. (Université McGill, 1975)
Keywords: Logement

Mutual Aid Networks in Two Feminist Housing Co-Operatives in Montreal - Yasmeen, Gisèle (Université McGill, 1991)
Keywords: Féminisme; Logement

A Comparison of Workforce Housing Practices in Three Cities and their Applicability to Montreal - Lazarovic, Rebecca (Université McGill, 2010)
Keywords: Logement; Travail

Landlord Subsidization by Tenants in East End Montreal - Kovitz, Marcia Mitzi Ruth (Université McGill, 1975)
Keywords: Locataires; Logement

Uncompleted Condominiums: A Strategy for Cost Reduction in Montreal Housing - Kowalska, Danuta (Université McGill, 1991)
Keywords: Logement

The Ownership of Old Rental Housing in an Appreciating Central Montreal Neighborhood - Roberts, Marilyn Manzer (Université McGill, 1972)
Keywords: Logement

Space about Multiple Dwellings with Special Reference to Montreal - Steber, George Jr. (Université McGill, 1963)
Keywords: Logement

The Restructuring of the Montreal Tourism Industry: A Sectoral Analysis - Pohlmann, Corinne (Université McGill, 1994)
Keywords: Tourisme

The Social Organization of Residential Real Estate - House, John Douglas (Université McGill, 1972)

Rethinking Trench Expressways: Urban Design Strategies with Applications to Montreal's Décarie Autoroute - Richer, Nadia (Université McGill, 2010)
Keywords: Autoroutes

Montreal Electric Streetcar Suburbanization: A Study of a Canadian City’s Morphological Transformation Before World War 1 - Karczmar, Christine Elizabeth (Université McGill, 2013)
Keywords: Banlieue; Tramways

L'article 29 de la convention de Montréal: clef de voûte de la responsabilité du transporteur aérien international - Chassot, Laurent (Université McGill, 2009)
Keywords: Aéroport

Vehicle-Pedestrian Accidents at Signalized Intersections in Montréal - Fernandes, David (Université McGill, 2013)
Keywords: Rues

The Feminization of Clerical Work in Early Twentieth-Century Montreal - Boyer, Laura Kate (Université McGill, 2001)
Keywords: Femmes; Travail

La discrimination sur le marché du travail: le cas des employés de bureau à Montréal - Dussault, Ginette (Université McGill, 1983)
Keywords: Femmes; Travail

The Nature of Women’s Employment with Special Reference to Montreal - Aikman, Mary E. (Université McGill, 1937)
Keywords: Femmes; Travail

Shortages of Skilled Blue Collar Workers in the Machining Trades in Montreal - Lépine, Irène (Université McGill, 1987)

Occupational Traits in Clerical Work: A Study of Employed and Unemployed Women in Montreal - Robertson, Barbara M. (Université McGill, 1935)
Keywords: Femmes; Travail

Examining the Overrepresentation of Black Males in the Young Offender System - Johnson, Druscilla (Université McGill, 2000)
Keywords: Délinquance; Noirs

"Doing it for the family": Educational Experiences of First-Generation Female Filipino Teens in Public Schools in Montreal - Pineda, Stephanie June (Université McGill, 2010)
Keywords: Philippins; Étudiants

Representing Twentieth Century Canadian colonial Identity: the Imperial Order Daughters of the Empire (IODE) - Pickles, Catherine Gillian (Université McGill, 1996)
Keywords: Britanniques; Femmes

Not a Place, but a Culture: The Cultivation of Iranian Subjectivity in Montreal - Hashemzadeh, Kianoosh (Université McGill, 2009)
Keywords: Iraniens

A Political Analysis of School Reorganization in Montreal - Fournier, Pierre (Université McGill, 1971)

Intégration et transnationalisme chez les Dominicains de Montréal - Dancause, Jacques-Luc (Université McGill, 2001)
Keywords: Caribéens

Cultural Sensitivity in the Context of Ethnic Polities: A Comparison of Two Families Service Agencies - Leung, Ho Hon (Université McGill, 2001)
Keywords: Chinois; Famille; Juifs

Independent Jewish Societies of Montreal. A Survey of the Nature and Extent of Philanthropic Programmes - 1949 - Shriar, Rupert (Université McGill, 1953)
Keywords: Juifs; Philanthropie

Political Economy, Transnationalism, and Identity: Students at the Montreal Hoshuko - Yoshida, Reiko (Université McGill, 2001)
Keywords: Japonais; Nationalisme

Life in an Urban Chassidic Community: Insulation and Proselytization. - Shaffir, William (Université McGill, 1972)
Keywords: Juifs

French and English in the Institutional Structure of Montreal: a Study for the Social and Economic Division of Labour - Jamieson, Stuart Marshall (Université McGill, 1938)
Keywords: Anglophones; Francophones

Reconstructing Tamil Masculinities: Kavati and Viratam among Sri Lankan Men in Montréal - Gross, Victoria (Université McGill, 2008)
Keywords: Sri Lankais

The Montreal Chassidic Community: Community Boundaries and the Maintenance of Ethnic Identity - Shaffir, William (Université McGill, 1969)
Keywords: Juifs

The Attitudes of Students of Greek Origin in a French-Language Learning Situation in a Québec Secondary School - Waite, Richard (Université McGill, 1991)
Keywords: Grecs; Langue; Étudiants

Identity, Place and Community: A Latin American Locale in Montreal - Occhipinti, Joseph (Université McGill, 1996)
Keywords: Latino-Américains

Young Second Language (L2) Learner's Meaning-Making: Consciousness, Collaboration, and Creativity (3Cs) - Kim, Mi Song (Université McGill, 2008)
Keywords: Coréens; Langue

Ethnicity as a Symbol System: a Theoretical Discussion Exemplified by Case Studies of Spaniards in Montreal - Fernandez, Ronald Louis (Université McGill, 1972)
Keywords: Espagnols

The Administration of Paris and Montreal: A Comparative Study - Pick, Alfred John (Université McGill, 1937)
Keywords: Fiscalité

Political Fragmentation, Municipal Expenditures, and Public Service Provision in the Montreal Metropolitan Area: A Study in Urban Political Geography - Barlow, I. Max (Université McGill, 1978)
Keywords: Bibliothèque centrale de Montréal; Fiscalité; Pompiers

Effective Public Consultations and Follow-Ups? Evaluating Montréal’s Municipal Public Hearing Processes in Large-Scale Urban Developments - Aubin, Raphaëlle (Université McGill, 2010)
Keywords: Griffintown; Pointe-Saint-Charles; Quartiers

Du silence à l'affirmation: Women Making History in Point St. Charles - Kruzynski, Anna (Université McGill, 2004)
Keywords: Femmes; Pointe-Saint-Charles; Quartiers

Prendre et trouver sa place: discours hétéronormatifs et pratiques hétérosexuelles dans un cruising bar de Montréal - Lebrun, Aurélie (Université McGill, 2003)
Keywords: Alcool

The Conservation of a Gender Fantasy: Women and Top 40 Radio in Montreal - Maki, Christine (Université McGill, 2008)
Keywords: Femmes; Radio

Homonormative Architecture & Queer Space: The Evolution of Gay Bars and Clubs in Montréal - Vallerand, Olivier (Université McGill, 2010)
Keywords: Alcool

Program Development at the University Settlement of Montreal - Mortin, Irving (Université McGill, 1953)
Keywords: Groupes populaires

Formalization in a Social Movement Organization: Cooptation or Survival? A Case Study of a Feminist Shelter for Battered Women - Nordquist, Karen L. (Université McGill, 1998)
Keywords: Femmes; Groupes populaires

A Study of Clothing Budgets on a Minimum Adequate Standard for a Family Agency in Montreal, 1947-1948 - Spector, Esther (Université McGill, 1948)
Keywords: Famille; Pauvreté; Vêtements

Implementing a Sex Education, STDs and HIV/AIDS Prevention Program in a Child Welfare Setting: Implications for Service Delivery - Di Sessa, Anna Maria (Université McGill, 2000)
Keywords: Enfants

Programmes intersectoriels pour les enfants exposés à la violence conjugale: recension des écrits et pistes d'actions pour la région de Montréal - Harper, Elizabeth (Université McGill, 2003)
Keywords: Enfants; Famille

Genesis of the Montreal Council of Social Agencies - Shepherd, William F. (Université McGill, 1957)
Keywords: Montreal Council of Social Agencies

Social Service in the Psychiatric Division of a General Hospital: A Study of Fifty-Three Patients of the Allan Memorial Institute of Psychiatry, Montreal, from 1950 to 1953 - Ginsberg, Elsie; Kinnis, Gladys (Université McGill, 1953)
Keywords: Hôpitaux; Hôpitaux psychiatriques; Montreal General Hospital

Montreal Association for the Blind: User Satisfaction Survey - McGraw, Cathy (Université McGill, 1997)

Intergovernmental Functions in Respect to Regional Planning: With Special Reference to the Region of Montreal - Feherdy, Laszlo Evan (Université McGill, 1969)

Urban Governance and Participatory Revitalization in Montreal: Two Case Studies of the Integrated Urban Revitalization (RUI) Policy - Kraemer, Sarah (Université McGill, 2012)

Participatory and Critical Out-of-School Learning for Urban Youth: Building Community through Popular Culture - Tan, Eloise (Université McGill, 2010)
Keywords: Musique

The Contribution of Dr. Sampson Paul Robins to Education in the Province of Québec: With Special Reference to the McGill Normal School - Kennedy, Mark Thomas (Université McGill, 1986)
Keywords: McGill Normal School

The Education of Non-Catholic English-speaking Physically Handicapped Children in Montreal - Milley, Chesley Boyd (Université McGill, 1957)
Keywords: Anglophones; Enfants

Critical Friends Groups at Lower Canada College: The Impact of Collaborative Communities on Teachers' Professional Growth and Classroom Practices - Moore, J. Brian (Université McGill, 2004)
Keywords: Enseignants; Lower Canada College

L'enseignement du solfège dans les écoles élémentaires de la Commission des Écoles catholiques de Montréal: Claude Champagne et ses contributions - Pilote, Gilles (Université McGill, 1970)
Keywords: Champagne, Claude; Commission des écoles catholiques de Montréal; Musique

The Theatre Arts Programmes at the Montreal Anglophone Cégep: A Study of their History, Philosophy and Development from 1967-1980 - Wyder, Patricia (Université McGill, 1981)
Keywords: Anglophones; Cégep; Théâtre

The Impact of the State of Israel on the Hebrew Curriculum of Two Jewish Elementary Schools in Montreal - Ziv, Benjamin (Université McGill, 1975)
Keywords: Israéliens; Juifs

Labyrinth: Cinema, Myth and Nation at Expo 67 - Whitney, Allison (Université McGill, 1999)
Keywords: Cinéma; Expositions

The Cemetery and Cultural Memory: Montreal Region, 1860 to 1900 - Watkins, Meredith G. (Université McGill, 1999)
Keywords: Cimetières

La Ville de Montréal et ses Bibliothèques Publiques - Chabot, Juliette (Université McGill, 1959)
Keywords: Bibliothèque centrale de Montréal

Imagining the City of Festivals: Festivalization and Urban Space in Montréal - Macdonald, Amy (Université McGill, 2012)
Keywords: Tourisme

The Physical Design of Alleys: An Evaluation of Alleys in the Montreal Plateau - Wise, David (Université McGill, 2004)
Keywords: Plateau Mont-Royal; Quartiers

Making Montreal's Indoor City Accessible for People with Disabilities - Hagg, Matthew (Université McGill, 2009)
Keywords: Espace souterrain

Movement, Morphology and Circulation of Montreal Summer Storms - Shaw, Roderick (Université McGill, 1970)
Keywords: Climat

Une étude bioclimatique de la ville de Montréal - Lafleur, Daniel (Université McGill, 1972)
Keywords: Climat

The Bias of Libraries: Montréal's Grande Bibliothèque - Mickiewicz, Paulina (Université McGill, 2013)
Keywords: Bibliothèque Saint-Sulpice; Bibliothèque centrale de Montréal; Bibliothèque nationale

Dynamics of Heavy Warm Season Precipitation Events in Montréal - Dookhie, Giselle C. (Université McGill, 2011)
Keywords: Climat

Visual Art/Public Art and Urban Development: A Case Study of Montreal (1967-1992) - Boyce, Margaret (Université McGill, 2001)
Keywords: Centre canadien d'architecture; Jardins; Squares

A Synoptic Climatology of Ground-Level Ozone for Montreal, Quebec - Stephens, Kate (Université McGill, 1995)
Keywords: Climat

A Synoptic Climatology of Montreal Precipitation - Fischer, Alexander P. (Université McGill, 1998)
Keywords: Climat

Climate and Architecture: With Special Reference to Montreal and Surroundings - Aronin, Jeffrey Ellis (Université McGill, 1951)
Keywords: Climat

Freezing Rain in the Montreal Area - Leech, Margaret E. (Université McGill, 1978)
Keywords: Climat

The Clustering of Skyscrapers with Special Reference to Montreal - Shank, Wesley Ivan (Université McGill, 1965)
Keywords: Gratte-ciel

The Petrology of a Part of Westmount Mountain near Summit Circle, Montreal - Malouf, Stanley Edward (Université McGill, 1936)
Keywords: Géographie physique

Planetary and Synoptic-Scale Analysis of Freezing Rain Events in Montreal, Quebec - Ressler, Gina (Université McGill, 2010)
Keywords: Climat

Recent Trends in Highrise Multiple House with Special Reference to the Rockhill Apartments, Montreal - Ghoshal, Prabhansu Kumar (Université McGill, 1969)
Keywords: Logement

Small Living Spaces: A Study of Space Management in Wartime Homes in Montreal - Pantelopoulos, Maria D. (Université McGill, 1993)
Keywords: Logement

The Evolution of Prefabricated Interior Components for Post-Occupancy Modification - Ou, Yangli (Université McGill, 1999)

Acoustics in Architectural Design: An Annotated Bibliography on Architectural Acoustics - Doelle, Leslie L. (Université McGill, 1964)

Preserving Old Buildings: Adaptive Use for Residential Purposes in Montreal - Vujadinovic, Milenko (Université McGill, 2002)
Keywords: Conservation; Patrimoine

Making the Creative City: A Case Study of the Quartier des Spectacles in Montreal - Loison, Laurie (Université McGill, 2013)
Keywords: Quartier des spectacles; Quartiers

New Urbanism in Practice: An Analysis of Five Greater Montreal Area Neighbourhoods - Vannelli, Jason (Université McGill, 2009)
Keywords: Griffintown; Quartiers; Rosemont; Saint-Laurent (ville); Île-des-Soeurs

Sky's the Limit: The Operations, Renovations and Implications of a Montréal Gay Bar - Allan, James (Université McGill, 1997)
Keywords: Alcool

[Re]Claiming Montreal’s Memory: Demolition and the Photography of Edith Mather - Southcott, Tanya (Université McGill, 2013)
Keywords: Patrimoine; Paysages; Photographie; Rues

Mixed Land Use Zoning with Special Reference to the Inner Cities of Montreal and New York City - Gumusyan, Garo (Université McGill, 1979)

Juvenile Delinquency in Montreal - Ross, Herman R. (Université McGill, 1932)
Keywords: Délinquance; Enfants

Les fonctions politiques du centre culturel: La Place des Arts et la Révolution tranquille - Illien, Gildas (Université McGill, 1995)
Keywords: Place des Arts; Places publiques

Women Prisoners and Modern Methods of Prison Control: A Comparative Study of Two Canadian Women's Prisons - Watson, Catherine M. (Université McGill, 1980)
Keywords: Femmes; Prisons

The Summit of Distinguished Living: Montreal's Gleneagles Apartments - Havekes, Luke Henry (Université McGill, 2011)
Keywords: Golden Square Mile; Logement; Quartiers

Le financement des services métropolitains et l’usage de la tarification, particulièrement dans le cas du service de la police dans la Communauté Urbaine de Montréal - Larin, Gilles (Université McGill, 1979)
Keywords: Communauté urbaine

Uses Made of a Mental Hygiene Clinic by a Boys’ Training School: How the Boys’ Farm and Training School at Shawbridge, Quebec Makes Referrals to and Uses the Treatment Recommendations of the Mental Hygiene Institute on Pine Avenue, Montreal - Mayotte, A. S. (Université McGill, 1949)

God's Mobile Mansions: Protestant Church Relocation and Extension in Montreal, 1850-1914 - Trigger, Rosalyn (Université McGill, 2004)
Keywords: Protestants; Églises

Human Scale in the Urban Design of Montreal Residential Developments - Lucic, Katija (Université McGill, 1995)
Keywords: Anjou; Banlieue; Centre-sud (quartier); Quartiers; Rues; Squares

Industrial Land Use in Urban Areas with Special Reference to Montreal - Sharma, Brajesh Chander (Université McGill, 1971)

Joseph Gould and the Montreal Mendelssohn Choir - Rice, Kelly Stanley (Université McGill, 1991)
Keywords: Musique

Le nationalisme et le radicalisme du journal La Patrie, 1879- 1897 - Laurin, L.-Luc (Université McGill, 1973)
Keywords: Nationalisme; Patrie (La)

Parent, Child, and Television: Interaction in Communication - Blais, Suzanne (Université McGill, 1962)
Keywords: Enfants; Famille; Télévision

Le réalisateur au réseau FM français de Radio-Canada - Vachon, Daniel (Université McGill, 1989)
Keywords: Radio; Radio-Canada

How Does what's Bred in the Bone Come Out in the Flesh? Devora Neumark's Interventions and the Concept of Flesh - Kiriloff, Vera (Université McGill, 2005)

Sexpo 67: Paradise Islands? Sexualized Space at the International and Universal Exposition in Montreal - Evans, Thomas (Université McGill, 2010)

Québec Electric: Montreal, Mutek and the Global Circuit - Schmidt, Patricia (Université McGill, 2010)

Man in his World, Children in Theirs: Material Culture at Expo '67 - Eilers, Frederika (Université McGill, 2010)

L'échec de la contestation au Québec depuis Borduas - Bonar, James de Gaspé (Université McGill, 1975)

The Practice of Engineering Geology during Pre-Construction Investigations in the Montreal Area - Eivemark, Michael M. (Université McGill, 1971)
Keywords: Géologie; Ingénieurs

Les troubles de 1860-1880 à Oka: choc de deux cultures - Pariseau, Claude L. (Université McGill, 1975)
Keywords: Autochtones; Communautés religieuses; Sulpiciens

L'histoire par l'image: commémoration picturale, pouvoir politique et stratégies visuelles au Québec (1880-1930) - Roy, Nathalie Anne (Université McGill, 2005)

Outdoor Play Areas for Children in High-Density Housing in Montreal - Aggarwal, Monica (Université McGill, 2001)
Keywords: Enfants; Parcs; Plateau Mont-Royal; Quartiers

Privacy in Row Houses of Montreal - Rahbar, Mehrdad (Université McGill, 1996)
Keywords: Logement

Secular and Parochial Education of Ashkenazi and Sephardi Jewish Children in Montreal: A Study in Ethnicity - Hirschberg, Jack Jacob (Université McGill, 1988)
Keywords: Enfants; Juifs

Shifting Cultures of Recycled Style: A History of Second-Hand Clothing Markets in Montreal - Diggins, Kimberly A. (Université McGill, 1998)
Keywords: Vêtements

The Changing Character of Streets in Central Areas with Special Reference to Sherbrooke Street as a Principal Street in City of Montreal-Canada - Rege, Ratan M. (Université McGill, 1966)
Keywords: Rues; Sherbrooke (rue)

The Stories Told: Indigenous Art Collections, Museums, and National Identities - Dickenson, Rachelle (Université McGill, 2005)
Keywords: Autochtones; Musées

Stewardship as Partnership: A Comparative Study of Positive Human-Environment Relationships in East Cree and Suburban Montreal Communities - Forrest, Margaret Anne (Université McGill, 2006)
Keywords: Banlieue; Parcs; Pointe-Claire

The Rebirth of the Shophouse in the Modern Age with a Special Reference to Montreal - Xu, Ti (Université McGill, 1998)
Keywords: Logement

The Royal Institution for the Advancement of Learning: The Correspondence, 1820-1829, a Historical and Analytical Study - Boulianne, Réal G. (Université McGill, 1970)
Keywords: Royal Institution for the Advancement of Learning

American and British Influences on Canadian News Content: As Shown by a Study of Two Montreal Newspapers - Radler, Ruth (Université McGill, 1930)
Keywords: Montreal Gazette; Montreal Star

Insuring against every man : an economic and social history of the Guarantee Company of North America, 1871-1919 - Doyon, Charles (Université McGill, 1980)
Keywords: Fiducie; Guarantee Trust Company

Ethnicity and Housing Adaptation: the Italians in Montreal - Fainella, John G. (Université McGill, 1986)
Keywords: Italiens; Logement

L’activité dramatique à Montréal de 1890 à 1900 - Larrue, Jean-Marc (Université McGill, 1979)
Keywords: Théâtre

The Development and History of the Federation of English Speaking Catholic Teachers, Incorporated, of Montreal - O'Brien, Michael (Université McGill, 1973)
Keywords: Enseignants; Federation of English Speaking Catholic Teachers

Crisis? What Crisis?: Anglophone Musicmaking in Montreal - Stahl, Geoff (Université McGill, 2003)
Keywords: Anglophones; Musique

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (Université McGill, 2000)
Keywords: Quartiers; Rues; Saint-Henri

Criminal Women and Bad Girls: Regulation and Punishment in Montreal, 1890-1930 - Myers, Tamara (Université McGill, 1996)
Keywords: Criminalité; Délinquance; Femmes; Prisons

Coping with the HIV and AIDS Epidemic in HIV Seronegative Gay Males in Montreal - Watson, Scott C. A. (Université McGill, 1999)
Keywords: Épidémies

The American Element in the Early Presbyterian Church in Montreal, 1786-1824 - Mcdougall, Elizabeth Ann (Université McGill, 1965)
Keywords: Presbytériens; Protestants; St Gabriel Street Presbyterian Church; St. Andrew and St. Paul (église); Églises

Broadway North: Musical Theatre in Montreal in the 1920s - Charpentier, Marc (Université McGill, 1999)
Keywords: Musique; Théâtre

Blanche Lemco van Ginkel and H.P. Daniel van Ginkel: Urban Planning - Hodges, Margaret Emily (Université McGill, 2004)

Authoritarianism, Constitutionalism and the Special Council of Lower Canada, 1838-1841 - Watt, Steven (Université McGill, 1998)
Keywords: Association constitutionnelle de Montréal (MCA); Loyalistes; Rébellions

A Survey of New Towns about Metropolitan Areas with Special Reference to Montreal - Kentridge, Leon R. (Université McGill, 1961)

A Study of Three Montreal Children's Theatres - Gold, Muriel (Université McGill, 1972)
Keywords: Enfants; Théâtre

A Study of the Outcome of Grade Repetition in the Protestant High Schools of Montreal - Gaite, Andrew J. H. (Université McGill, 1966)
Keywords: Bureau des écoles protestantes

A Survey of Industrial Estates with Special Reference to Montreal - Grasser, Otto (Université McGill, 1964)

A Study of Recreation in a Rapidly Developing Community in Montreal - Faughnan, Jeanne; Gabois, Denise; Miller, Robert; Ozier, Morris; Romer, Gabrielle; Sinuk, Morris (Université McGill, 1953)
Keywords: Quartiers; Saint-Laurent (quartier)

A Sense of Belonging: Pre-Liberation Space, Symbolics, and Leadership in Gay Montreal - Higgins, Ross (Université McGill, 1997)

Art, identité et Expo 67. L'expression du nationalisme dans les œuvres des artistes québécois du Pavillon de La Jeunesse à l'Exposition universelle de Montréal - Hellman, Michel (Université McGill, 2005)
Keywords: Expositions; Nationalisme

A Neighborhood that Empowers Women: In Search of Housing Sustainability - Insaf, Zeenat S. (Université McGill, 1999)
Keywords: Femmes; Logement

A Sociological Study of Three Philanthropic Financial Campaigns in Montreal - Blishen, Bernard R. (Université McGill, 1950)
Keywords: Philanthropie

An Account of English Journalism in Canada from the Middle of the Eighteenth Century to the Beginning of the Twentieth, with Special Emphasis Being Given to the Periods Prior to Confederation - Read, S. M. E. (Université McGill, 1925)
Keywords: Anglophones; Gazette Littéraire de Montréal; Minerve (La); Montreal Gazette; Montreal Herald; Montreal Witness

Analyticity in Montreal Swedish - Gadelii, Karl Erland (Université McGill, 1988)
Keywords: Suédois

An Evaluation of the Old Age Pension System in Canada: An Analysis Based on the Socio-Economic Needs of One Hundred Aged Clients of the Family Welfare Association of Montreal - Jewett, Marion Shiell (Université McGill, 1949)

Analyse sociolinguistique de deux discours féministes - Helme, Mireille (Université McGill, 1984)
Keywords: Féminisme; Les Têtes de Pioche (journal)

An Analysis of the Organizational Practices and Educational Effects on the Quebec Board of Black Educators - Brathwaite, Gilbert (Université McGill, 1986)
Keywords: Bureau des écoles protestantes; Noirs

Constructing Italian Ethnicity: A Comparative Study of Two Italian Language Newspapers in Australia and Canada, 1947-1957 - Iuliano, Susanna (Université McGill, 1994)
Keywords: Italiens

Columns on the March: Montreal Newspapers Interpret the Spanish Civil War, 1936-1939 - Charpentier, Marc (Université McGill, 1992)
Keywords: Canada (Le); Clarté; Devoir (Le); Illustration Nouvelle (L'); Jour (Le); Journalistes; McGill Daily; Monde ouvrier (Le); Montreal Standard; Montreal Star; Montréal-Matin; Unité (L')

Coming into Site: Identity, Community and the Production of Gay Space in Montréal - Doyle, Vincent André (Université McGill, 1996)

Chinese-Canadian Women in Montreal: Case Studies in the Importance of Education - Li, Sharon (Université McGill, 1995)
Keywords: Chinois; Femmes

Imagining Ethnicity. The Role of the Montreal Bangladeshi Press in Ethnic Cohesion - Ahmed, Shameem (Université McGill, 1997)
Keywords: Bengalis

The Adjustment of Israeli Immigrant Students in Montreal - Gutstadt, Pnina (Université McGill, 1996)
Keywords: Israéliens; Juifs; Étudiants

Captives in Canada, 1744-1763 - Gray, Colleen (Université McGill, 1993)
Keywords: Autochtones; Britanniques; Captifs

Can Transit and Spatial Planning Synergy Work at the Regional Scale? Understanding Metropolitan Transit-Oriented Development Planning and its Challenges in the Canadian City-Regions of Toronto, Montreal and Vancouver - Hamzah, Muhammad Zulkarnain (Université McGill, 2013)
Keywords: Transport en commun

A Study of the Expressed Employment Needs of the Montreal Business Community with Implications for the Business Education Curriculum - Upton, Phyllis G. (Université McGill, 1966)

Between the Lines: Interartistic Modernism in Canada, 1930-1960 - Rackham, Michèle (Université McGill, 2012)
Keywords: Peinture; Poésie; Sculpture

The Montreal Parks and Playgrounds Association Inc. A Historical Study of the Association from the Year of Its Founding in 1896 to 1949 - Wilson, E. Laird (Université McGill, 1953)
Keywords: Montreal Parks and Playgrounds Association; Parcs

The Montreal Young Men's Christian Association as a Religious and Social Organization - Davis, Richard E. (Université McGill, 1927)
Keywords: YMCA

Development of Cote A Baron - Marshall, Robert S. (Université McGill, 1983)
Keywords: Baron (côte à)

Ames as Municipal Reformer - Russell, Daniel J. H. B. (Université McGill, 1972)
Keywords: Ames, Herbert Brown; Réformistes

Imported Devotions: Roman Catacomb Saints in Ultramontane Montreal - Dahan, Michel (Université McGill, 2014)
Keywords: Reliques; Ultramontains; Églises

There's No Place Like Home: Feminist Communities, Social Citizenship and (Un)Belonging in Montreal's Long Women's Movement, 1952-1992 - Ricci, Amanda (Université McGill, 2015)
Keywords: Anglophones; Autochtones; Femmes; Francophones; Féminisme; Haïtiens; Italiens; Noirs

A captivating ''Open City'': the production of Montreal as a ''wide-open-town'' and ''ville ouverte'' in the 1940s and '50s - Kuplowsky, Adam (Université McGill, 2014)
Keywords: Alcool; Criminalité; Délinquance; Prostitution

Beyond the Decline: Revaluing Montreal's Movie Palaces - Heather Gibb, Alexandra (Université McGill, 2015)
Keywords: Cinéma; Conservation; Patrimoine

A Community of Believers and Healers: Learning from the functional characteristics of Hôtel Dieu - McDonald, Marie-Pierre (Université McGill, 2014)
Keywords: Communautés religieuses; Hôpitaux; Hôtel-Dieu

Francois Marie Perrot and the Isle Perrot - Scott Wardleworth, Eleanor (Université McGill, 1931)
Keywords: Perrot, François-Marie

Shaping Time in the City: A Cultural History of Concrete Modernity in Montreal, 1903-2015 - Charles, Julia Morgan (Université McGill, 2015)
Keywords: Autoroutes; Béton; Port; Stade olympique

Languages in Contact: Error Analysis of Italian Childrens' Compositions in a Multilingual Context - Samperi Mangan, Jacqueline (Université McGill, 1991)
Keywords: Enfants; Italiens; Langue

La letteratura dell'emigrazione italo-canadese di Montréal - Tedeschi, Antonio (Université McGill, 2000)
Keywords: Italiens

Jewish Supplementary Schooling in Montreal in the Latter Part of the Twentieth Century - Segal, Sima (Université McGill, 1991)
Keywords: Bureau des écoles protestantes; Juifs; Langue

Intra-Ethnic Differences of the Perceptions of Aged Italian Women in Receiving Care - Bonar, Rita Aguzzi (Université McGill, 1993)
Keywords: Femmes; Italiens

In the Shadow of the Mountain: A Historical Re-Evaluation of the 1988 Outremont Dispute - Herman, Dana (Université McGill, 2003)
Keywords: Juifs; Outremont

Italian Identity in Montreal: Issues of Intergenerational Ethnic Retention - De Martinis, Lucio (Université McGill, 2005)
Keywords: Italiens

In Search of Communal Identity: The Role of the Black Community in Identity Formation among Nigerian Youth - Ogbuagu, Buster C. (Université McGill, 2007)
Keywords: Nigériens; Noirs

Immigration, Ethnicity, and the Labour Market: The Chinese in Montreal - Pao-Mercier, Laura Yrien-Ha (Université McGill, 1982)
Keywords: Chinois; Travail

Hometown and Family Ties: The Lebanese-Syrians of Montreal, 1905-1950 - Moser, Diane (Université McGill, 1990)
Keywords: Libanais; Syriens

Hearing (Unheard) Voices: Aboriginal Experiences of Mental Health Policy in Montreal - Macdonald, Mary Ellen (Université McGill, 2003)
Keywords: Autochtones

Growing Up in Three Languages: Triliteracy Practices of Chinese Immigrant Children in Quebec - Curdt-Christiansen, Xiao Lan (Université McGill, 2003)
Keywords: Chinois; Langue

Gender, Race, and Power: the Chinese in Canada, 1920-1950 - Huang, Belinda (Université McGill, 1998)
Keywords: Chinois

Family, Paesani and Networks: Politics and Economy of Montreal Italians - Aramaki, Michiko (Université McGill, 1994)
Keywords: Italiens

The Emigration of Adam Smith's Ploughman: A Case Study of the Intellectual Culture of Scots Emigrants to Lower Canada, 1760-1850 - Gibson, Sarah Katherine (Université McGill, 2007)
Keywords: Écossais

The Irish in the Province of Canada in the Decade Leading to Confederation - Lyne, Daniel Colman (Université McGill, 1960)
Keywords: Irlandais

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

HIV Risk Behaviour and Predictors of Initiation into Prostitution among Female Street Youth in Montreal, Canada - Weber, Amy E. (Université McGill, 2001)

Le journal Canada-Revue et Mgr Édouard-Charles Fabre, 1890-1895 - Jetté, Pierre (Université McGill, 1972)
Keywords: Canada-Revue; Fabre, Édouard-Charles; Évêques

The Montreal Gazette and Honoré Mercier, 1886 to 1892 - Rose, Ian (Université McGill, 1968)
Keywords: Montreal Gazette

Integrating Islam: A Muslim School in Montreal - Kelly, Patricia (Université McGill, 1997)
Keywords: Musulmans

Housing the Grey Nuns: Power, Religion and Women in fin-de-siècle Montréal - Martin, Tania Marie (Université McGill, 1995)
Keywords: Communautés religieuses; Couvents; Soeurs Grises

Upper Class Reaction to Poverty in Mid-Nineteenth Century Montreal: A Protestant Example - Harvey, Janice (Université McGill, 1978)
Keywords: Pauvreté; Protestants

The Role of the Parish in Fostering Irish-Catholic Identity in Nineteenth-Century Montreal - Trigger, Rosalyn (Université McGill, 1997)
Keywords: Irlandais; Notre-Dame (paroisse)

When Nationalisms Collide: Montreal's Italian Community and the St. Léonard Crisis, 1967-1969 - D'Andrea, Giuliano E. (Université McGill, 1989)
Keywords: Italiens; Saint-Léonard (crise de)

West Indian Associations in Montreal - Handelman, Don (Université McGill, 1964)
Keywords: Caribéens; Clubs

L'Action française de Montréal - Baer, Ginette (Université McGill, 1977)
Keywords: Action française (L')

Race and beauty in Canada: print culture, retail, and the transnational flow of products, images and ideologies, 1700s to present - Thompson, Cheryl (Université McGill, 2014)
Keywords: Esclaves; Noirs

Single Room Occupancy (SRO) for Montreal’s Homeless Population - Rubial Carvajal, Isabella (Université McGill, 2016)
Keywords: Logement; Pauvreté

Veillées, Variants, and Violoneux: Generic boundaries and transnational trajectories in the traditional instrumental music of Quebec - Risk, Laura (Université McGill, 2016)
Keywords: Chanson; Musicien; Musique

The Sattikka, the Turban and the Spices, the Cultural Landscape of a South Asian Neighbourhood: A Study on the Ethnic Diversity in Contemporary Montreal - Islam, Khadiza (Université McGill, 2016)
Keywords: Bengalis; Pakistanais; Parc-Extension (quartier); Quartiers; Sri Lankais

Imagining Sufism and Muslimness: the production of knowledge about Sufism and its power against political Islam in the United States, Canada, and Pakistan - Mercier-Dalphond, Geneviève (Université McGill, 2017)
Keywords: Musulmans

Bilinguefact your air: literary representations of French Canada, 1945-48 - Isler, Julia (Université McGill, 2017)
Keywords: Anglophones; Bilinguisme; Francophones; Roman

"Temple of my Heart": Understanding religious space in Montreal's Hindu Bangladeshi Community - Bhattacharjee, Aditya (Université McGill, 2017)
Keywords: Bengalis; Hindous

Distribution ambiances magnétiques etcetera and constellation records: DIY record labels and the Montreal experimental music scene - Mouillot, Francois (Université McGill, 2017)
Keywords: Musicien; Musique

Blackness, exclusion, and the law in the history of Canada’s public schools, Ontario and Québec, 1850–present - Zellars, Rachel (Université McGill, 2017)
Keywords: Noirs

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith, Donald

Defining their Situation: The Experience of Long Term Mental Patients in an Asylum Committed to Non-Institutional Treatment - Myers, N. Marybelle (Université McGill, 1979)
Keywords: Hôpital Douglas; Hôpitaux psychiatriques

La poésie en langue des signes et ses usages à Montréal (1960-2017) - Daigneault, Catherine (Université McGill, 2018)
Keywords: Langue; Poésie; Sourds

The many worlds of Louis Riel: a political odyssey from Red River to Montreal and back 1840-1875 - Hamon, Max (Université McGill, 2017)
Keywords: Collège de Montréal; Communautés religieuses; Sulpiciens

A Voice of English-Montreal. The First Twenty Years of Véhicule Press, 1973-1993 - Hemond, Amy (Université McGill, 2019)
Keywords: Imprimerie; Poésie; Édition

Envisioning new futures: Portrait photographs of black Victorians in Montreal, 1861-1901 - Evoughlian, Sandra (Université McGill, 2018)
Keywords: Noirs; Notman, William; Photographie

Faubourg des Récollets: projet de mise en valeur - Malo, Pierre (Université McGill, 1991)
Keywords: Faubourgs

Settling an 18th Century Faubourg: Property and Family in the Saint-Laurent Suburb, 1735-1810 - Stewart, Alan M. (Université McGill, 1988)
Keywords: Famille; Faubourgs; Quartiers; Saint-Laurent (quartier)

Identity construction of Chinese immigrants: Exploring the processes of identity construction among Chinese immigrant parents and young adults in Montreal - Qian, Lingwei (Université McGill, 2016)
Keywords: Chinois; Quartier chinois; Quartiers

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Honnêtes hommes et gentilshommes : L'éducation classique des garçons et la formation du soi masculin au Bas-Canada à l’âge des révolutions (1791-1840) - McCutcheon, Shawn (Université McGill, 2021)
Keywords: Collèges classiques

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman, William; Photographie; Écossais

Black slavery, historians and textbooks: A study of the representation of enslaved people of African descent in Quebec's historiography and history textbooks - Roethlisberger, Susanne (Université McGill, 2020)
Keywords: Africains; Esclaves; Histoire

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

Social Transformation in Notre Dame de Grâce over the Long Sixties - Kastner, Jeffrey (Université McGill, 2023)
Keywords: Centres d'acceuil

The McTavish Pumphouse - Maffini, Giulio (Université McGill, 1970)
Keywords: Aqueduc; Mont Royal

The Expansion of the University of Montreal in the 60' - Weiser, Fred (Université McGill, 1968)
Keywords: Université de Montréal

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

Bonsecours Market and its Historical Site - Gunars, Janitens (1963)
Keywords: Marchés